Genome-Wide Identification of DOG1 Domain Containing Proteins and Their Role in Moisture Deficit Stress Tolerance in Tomato - Hara Gopal Krishnajee; Senthil Kumar Avinash; Dayanandhi Elangovan; Malarvizhi Mathiazhagan; Avvaerahally Thammannagouda Sadashiva; Laxman Ramanna Hunashikatti; Kumudini Belur Satyan; Kundapura V. Ravishankar (Plant Molecular Biology Reporter, 2026)

Decoding the biotic networks and functional potential of seamount sediments in the Arabian sea - Senthil Alias Sankar; Sneha Kalasseril Girijan; Yashwanth Belathur Shambhugowda; Siva Kiran Kumar Busala; Saravanane Narayanane (Molecular Biology Reports, 2026)

Probabilistic safety assessment in medical cyclotron facilities - C. Senthil Kumar; Suvadip Roy; Tapan Routh; M. Senthilkumar (Annals of Nuclear Energy, 2026)

Terpene-based biofuels production: a revolutionizing role of cyanobacteria through metabolic engineering, opportunities and challenges - Aakash Kamalesan; K. K. Kumar; Bharathi Nathan; Renukadevi Perumal; Senthil Natesan; Vellaikumar Sampathrajan (Archives of Microbiology, 2026)

Computational study on wave attenuation by an inclined porous-plate wave barrier - V.S. Hari Vijayan; Senthil Kumar Natarajan; Il Hyoung Cho (Ocean Engineering, 2026)

Exploring the performance of pressure swing adsorption for upgradation of biogas using zeolite as a suitable media - Sanchali Bose; Senthil Rathi B; P. Senthil Kumar; Moses Prabu H; Gayathri Rangasamy; N. Vijai (Next Research, 2026)

Quinone-fused diazepine π-conjugated carbon black: A chemically induced, topological-defect like engineered platform for ultrastable redox activity and ultrasensitive electrocatalytic sensing of ascorbic acid - Kumar Sandhya; Sugumar Monisha; Rajan Reshma; Krishnan Ashokkumar; K. Sriraghavan; Annamalai Senthil Kumar (Chemical Engineering Journal, 2026)

Circular upcycling of waste toner into eco-safe superparamagnetic nano-Fe3O4@C core–shell pigment for sustainable magnetic leather coatings - Sandipan Chatterjee; Nayan Sarkar; Surabhi Dipali Muduli; Chirasmita Das; Jit Sarkar; Arghyadip Bhowmik; Sathish Murali; Senthil Kumar Ganesan (Journal of Environmental Management, 2026)

Exploring the unknown territory of dromions of (2+1) dimensional generalized nonlinear Schrödinger equation - C. Senthil Kumar; R. Radha (Wave Motion, 2026)

Retraction notice to “Bioconversion of municipal solid waste into bio-based products: A review on valorisation and sustainable approach for circular bioeconomy” [Sci. Total Environ. 748 (2020) 141312] - P.R. Yaashikaa; P. Senthil Kumar; A. Saravanan; Sunita Varjani; Racchana Ramamurthy (Science of The Total Environment, 2026)

RNA interference (RNAi) in agriculture: Revolutionizing crop improvement and sustainable crop protection - A. Thanvarshni; G. Senthil Kumar; R. Sathya Priya; R. Sivakumar; D. Muthumanickam; S. Pazhanivelan; R. Krishnan (Physiological and Molecular Plant Pathology, 2026)

Mitigating strategies adopted for the treatment of mining wastewater: A review - Chandrika Sengar; Ashish Kapoor; Ponnusamy Senthil Kumar; Gayathri Rangasamy (Journal of Geochemical Exploration, 2026)

Chitosan-based azadirachtin nanoemulsion: A multi-target approach for effective management of Bemisia tabaci (Gennadius) through biochemical, molecular, and field evaluation - Vishnu Murugesan; Kannan Malaichamy; Samyuktha Senthil Kumar Sakthiyavathi; Dineshkumar Selvaraj; Madesh Kamalakannan; Santhiya Panchalingam; Soundararajan Raga Palanisamy; Suganthi Angappan; Subramanian Alagesan; Senthilkumar Murugaiyan; Rameash Kuppusamy; Govindaraju Kasivelu (Journal of Asia-Pacific Entomology, 2026)

Retraction notice to “A review on extraction of polysaccharides from crustacean wastes and their environmental applications” [Environ. Res. 221 (2023) 115306] - A. Saravanan; P. Senthil Kumar; D. Yuvaraj; S. Jeevanantham; P. Aishwaria; P.B. Gnanasri; M. Gopinath; Gayathri Rangasamy (Environmental Research, 2026)

Streamflow dynamics under integrated land use-climate change impacts in the Upper Krishna Basin, India - Richa Pandey; Ajay Ahirwar; Sukant Jain; Annamalai Ramalingam Senthil Kumar; Anil Kumar Lohani (Environmental Science and Pollution Research, 2026)

Topographic and Land Use Driven Land Surface Temperature Dynamics in a Fragile Lesser Himalayan Catchment - Pravin Rangrao Patil; Harsh Upadhyay; Disha Yadav; Manish Kumar Nema; A. R. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Mesoporous silica nanoparticles for postharvest protection of cowpea seeds: physicochemical characterization, insecticidal activity, and impacts on seed quality and antioxidant systems - Kannan Malaichamy; Madesh Kamalakannan; Elango Kolanthasamy; Govindaraju Kasivelu; Balakumbahan R; Dineshkumar Selvaraj; Samyuktha Senthil Kumar Sakthiyavathi; Vishnu Murugesan (Biocatalysis and Agricultural Biotechnology, 2026)

Plant-Mediated CuO Nanoparticles for Reactive Orange Dye Adsorption: Experimental study and Machine Learning-Assisted Optimization - S. Murugeshwari; Madhan Gunasekaran; B. Senthil Rathi; R. M. Saravana Kumar; J. Divya (Water, Air, & Soil Pollution, 2026)

Variable Secondary Metabolites for Defense Against Chilo Partellus (Swinhoe) and Sesamia Inferens (Walker) in Maize - Mukesh Kumar Dhillon; Tanmaya Kumar Bhoi; Ashok Kumar Sau; Sengottayan Senthil-Nathan (Journal of Chemical Ecology, 2026)

Comparative microbiome profiling of plant- and animal-derived traditional fermented foods from Mizoram, India using full-length 16S rRNA sequencing - Jacinta Lalhmunsangi; Rajkumar Sudharsan; Gracy Laldinmawii; Rebecca Lalngaihzuali; Madhuchhanda Das; Samaresh Das; Subhankar Mukherjee; Soumyadeb Bhattacharyya; T. Ramamurthy; Parimal Roychoudhury; Fatema Akter; Ashis Mukhopadhyay; et al. (Antonie van Leeuwenhoek, 2026)

Metabolic engineering strategies: utilizing different microbial strains and advanced technologies for the synthesis of high-valued terpenoids - Aakash Kamalesan; K. K. Kumar; Bharathi Nathan; Renukadevi Perumal; Senthil Natesan; Vellaikumar Sampathrajan (Antonie van Leeuwenhoek, 2026)

Development and evaluation of sub-tropically adapted sweet corn hybrids for dual-purpose utilization with emphasis on yield and fodder quality traits - Puja Mandal; Babu Chakrapani; Vignesh Muthusamy; Brijesh Kumar Mehta; Parameshwaran Mathavaraj; Rashmi Chhabra; Senthil Natesan; Chandrakumar Kalichamy; Kumari Vinodhana Natarajan; Rajkumar Uttamrao Zunjare; Javaji Chandra Sekhar; Ravikesavan Rajasekaran; et al. (The Nucleus, 2026)

Correction to: Clean Hydrogen Fuels from Artocarpus Heterophyllus Peel Waste: Supercritical Water Gasification Enhanced by a Multi-Metal Biochar– Perovskite Catalyst - Srinivasa Reddy Nallimilli; Renu Sharma; Vinayagam Mohanavel; Rekha M. M; Sathish Kannan; Senthil Kumar Vishnu; Ashwin Jacob; Elumalai Vengadesan; Praveen Barmavatu (BioEnergy Research, 2026)

Highly efficient electrochemical sensor for sulfamerazine detection in water using Ru nanoparticle/polypyrrole-modified acid-etched halloysite nanotubes - Balamurugan Senthil Kumar; Thanh-Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong (Journal of Water Process Engineering, 2026)

Unlocking early-generation potential: selection of TGMS-based breeding material in F2 and F3 generations of rice - Bhavna Baxla; Kalaimagal Thiyagarajan; Manonmani Swaminathan; Anita Bellie; Sritharan Natarajan; Senthil Kumar Govindan (Euphytica, 2026)

Optimized extraction and characterization of Turbinaria ornata-derived sodium alginate for controlled release of indole-3-acetic acid in plant growth enhancement - Vasubalan Manivinoth; Pk. Senthil kumar; Satish Lakkakula; Monica Durairaj; Hosimin Selvaraj; Kavitha Thangavel (Algal Research, 2026)

Phytochemical and antioxidant properties of Kedrostis foetidissima and its larvicidal potential against mosquitoes - Ayyadurai Thirumurugan; Meenaloshini Padmanaban; Durairaj Sathish Kumar; Rajagopal Govindharaju; Sethuramasamy Padmavathy; Velusamy Karthikeyan; Thiruppathi Senthil Kumar; Sivabalan Karthik (South African Journal of Botany, 2026)

Age dating, geometry and movement direction of a 411 km long lunar lobate scarp complex: Evidence of recent tectonism on the far side of the moon - Abhisek Mishra; P. Senthil Kumar (Planetary and Space Science, 2026)

Assessing the genetic variation using simple sequence repeat markers and biochemical analysis of turkey berry (Solanum torvum Swartz.) - Nitish Kumar Jena; Peria Nadar Irene Vethamoni; Thiruvenkatasamy Saraswathi; Senthil Natesan; Arumugam Nithyanandam; Arun Arunachalam; Ranjan Kumar Jena; Abinash Mishra (The Nucleus, 2026)

Accelerated development of prolific sterility maintainer lines in maize (Zea mays L.) using doubled haploidy for baby corn hybrid breeding - R. K. Khulbe; Devender Sharma; Arunava Pattanayak; G. S. Bisht; M. C. Pant; V. K. Pandey; Bhawana Bisht; Senthil Kumar; Priya Garkoti (Euphytica, 2026)

Retraction Note: Carbon dioxide methanation on heterogeneous catalysts: a review - Cham Q. Pham; Mahadi B. Bahari; Ponnusamy Senthil Kumar; Shams Forruque Ahmed; Leilei Xiao; Sunil Kumar; Amjad Saleh Qazaq; Tan Ji Siang; Huu-Tuan Tran; Aminul Islam; Adel Al‑Gheethi; Yasser Vasseghian; et al. (Environmental Chemistry Letters, 2026)

Clean Hydrogen Fuels from Artocarpus Heterophyllus Peel Waste: Supercritical Water Gasification Enhanced by a Multi-Metal Biochar–Perovskite Catalyst - Srinivasa Reddy Nallimilli; Renu Sharma; Vinayagam Mohanavel; Rekha M. M; Sathish Kannan; Senthil Kumar Vishnu; Ashwin Jacob; Elumalai Vengadesan; Praveen Barmavatu (BioEnergy Research, 2026)

Multi-objective optimization of an oscillating wave surge converter with a partially permeable flap using XGBoost and NSGA-II - Senthil Kumar Natarajan; Il Hyoung Cho (Ocean Engineering, 2026)

Improving solar postharvest drying through integrations of PANI–Fe3O4 nano-coated flat plate collectors with PCM-assisted heat recovery - Xing-Wei He; Manzoore Elahi M. Soudagar; Nagaraj Basavegowda; Raghuvaran Sivanandham; Sathish Kannan; Vinayagam Mohanavel; Senthil Kumar Vishnu; Manikandan Ayyar (Journal of Stored Products Research, 2026)

Integrated evaluation of direct-expansion solar-assisted heat pump systems with climate-compatible refrigerants using life cycle impact and cost metrics - Arunkumar Munimathan; K. Senthil Kumar; M. Kannan; Ratchagaraja Dhairiyasamy; Mamdooh Alwetaishi; Ali Keçebaş (Energy and Buildings, 2026)

Isolation, characterization of endophytic mycobionts and their utilization for the acclimatization of in vitro propagated plantlets of Anoectochilus elatus – a near threatened terrestrial jewel orchid - N. Ahamed Sherif; J. H. Franklin Benjamin; M. N. Abubacker; T. Senthil Kumar; M. V. Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Joint estimation of directional wave and wind spectra from floating offshore wind turbine motions using deep learning - Byungho Kang; Semyung Park; Daeyong Kwon; Il Hyoung Cho; Senthil Kumar Natarajan (Ocean Engineering, 2026)

Microbial conversion of banana pseudostem scutcher waste into xylitol using Candida tropicalis (PV544892) - Paramasivam Suresh Kumar; Nayana Chathalingath; Magesh Kumar Birundha; Renga Nathan Senthil Kumar Kabilan; Rajendran Arthee (Food Research International, 2026)

Unraveling pesticide impacts on pollinators: a global challenge for sustainable crop protection - G. Srivani; G. Senthil Kumar; M. Djanaguiraman; R. Sathya Priya; R. Sharmila; P. Murali Arthanari; P. Malathi; K. Raja; P. Parasuraman (The Science of Nature, 2026)

Evaluation of the Protective Effect of Sargassum Polycystum Biomass Derived Byproducts Against Cisplatin Induced Liver and Renal Damage in Albino Rats - Annamalai Natarajan; Radhakrishnan Prabakarakrishnan; Parthiban Janani; Velayutham Veeramani; Govindaswamy Padmapriya; Balasubramanian Senthil Kumar (Journal of Pharmaceutical Innovation, 2026)

Prophylactic and Immunomodulatory potential of gooseberry (Phyllanthus acidus) and oregano (Coleus amboinicus) extracts against tilapia lake virus (TiLV) in tilapia - Sekar Gobinath; Bagthasingh Chrisolite; Panchavarnam Sivasankar; P. Senthil Kumar; Anix Vivek Santhiya; Palaniappan Subash; M. Mohamed Mansoor; Muthumariappan Selvamagheswaran; Paulraj Magesh Kumar (Archives of Virology, 2026)

Work function–engineered high-entropy oxide for low-voltage glucose oxidation and hydrogen generation - Gyeong-Ah Kim; Jayesh Cherusseri; Raja Arumugam Senthil; Anuj Kumar; Jangyun Kim; Sagyntay Sarsenov; Mohd Ubaidullah; Myong Yong Choi (Chemical Engineering Journal, 2026)

Towards climate-smart crops: advances in plant stress biology research - Muthappa Senthil-Kumar (Journal of Plant Biochemistry and Biotechnology, 2026)

Genetic dissection of photoperiod response in Indian proso millet (Panicum miliaceum L.) mutants via BLUP modeling of photothermal indices - Ayushi Kumar; Iyanar Krishnamoorthy; Manikanda Boopathi Narayanan; Senthil Alagarswamy; K. Chandrakumar; Mehanathan Muthamilarasan; Ravikesavan Rajasekaran (Journal of Plant Biochemistry and Biotechnology, 2026)

Identification of QTLs Responsible for Fodder Quality Traits in Fodder Maize (Zea mays L.) - Pawan Kumar Dash; Palaniyappan Subramani; Ganesan Kalipatty Nalliappan; Manivannan Narayana; Vellaikumar Sampathrajan; Senthil Natesan (Indian Journal of Genetics and Plant Breeding, 2026)

The electrochemical sensor for sulfamerazine detection in water based on polypyrrole-decorated halloysite nanotubes - Balamurugan Senthil Kumar; Raja Nehru; Cheng-Di Dong (Applied Clay Science, 2026)

Gonadal Stage Identification and Oocyte Size Measurement Using DL Integrated Ultrasonography in Asian Sea Bass Lates calcarifer (Bloch, 1790) - Thakkarajan Senthil Murugan; Dani Thomas; Aritra Bera; Marappan Makesh; R. Annie Uthra; J. Preetha Roselyn; Samiappan Dhanalakshmi; Saad Yunus Sait; Sani Meenakshi; Selvam Thamizhazhagan; Govindarajan Thiagarajan; Muniyandi Kailasam; et al. (New Zealand Journal of Marine and Freshwater Research, 2026)
This study investigated gonadal stages in Asian sea bass ( Lates calcarifer ) using portable ultrasonography (Sonosite Edge II, 6–13 MHz), with histological validation of female (primary oocyte, early vitellogenic, ripe) and male (ripe) stages. Distinct echogenicity patterns differentiated sexes, and ultrasound‐based gonad measurements showed strong correlations with actual dimensions (ovary length R 2 = 0.9942, ovary width R 2 = 0.9886, testis length R 2 = 0.9857, testis width R 2 = 0.9793). Deep learning models achieved 99.9% accuracy for sexual maturity prediction (DenseNet‐161) and 99.8% for sex classification (VGG16). CNN regression with L1 and L2 regularization was used to predict oocyte diameters. The MAE (mean absolute error) was 6.31 µm for minimum and 5.20 µm for maximum oocyte diameter, which is less than 1.82% of the actual oocyte diameter (256–544 µm). These results, along with averaging over 10‐fold and small confidence intervals, indicate the robustness of the classification and regression methods. This raises the possibility of automating the classification of the fish reproductive stage by combining deep learning with ultrasound technologies and further developing contactless underwater ultrasonographic assessment of gonadal maturation in commercially important fin fish species. It also reduces the dependency on experts to infer sexual maturation details from ultrasound scans. The developed machine learning model is deployed in real‐time processor, Nvidia Orin, through which real‐time testing is carried out and the results are validated.

Polystyrene microplastics alter physiological parameters in the Drosophila model - Sharine Priscilla; Ryo Nagasawa; Swetha Senthil Kumar; Meenakshi Podwal; Sai Charan Kasavaraju; Chirayu Chandrakanth; Premkumar Sivakumar; Hamsini Bharat; Iyeswaran Muthulingam; Masakazu Umezawa; Sahabudeen Sheik Mohideen (Environmental Science and Pollution Research, 2026)

Assessing the impact of microplastic polymer wastes on environmental fate and human health risks - Maria Joseph Angelaa Lincy; Senthil Kumar Babu; Saghya Infant Shofia; Senthilkumar Nangan; Balamurugan Paneerselvam (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Sea-level and basement structural controls on Late Quaternary sedimentation in a tropical wave-dominated delta: Evidence from subsurface cores in Kaveri Delta, India - Kartika Goswami; Linto Alappat; Manoj K. Jaiswal; Sivakumar Krishnan; Anbarasu Kumaresan; Senthil Kumar Sadasivam; Xianjiao Ou (Marine Geology, 2026)

Optimizing a standard protocol for protocorm-like bodies induction and mass propagation of Coelogyne mossiae plantlets for efficient evaluation of pharmaceutical potential - Shivakrishnan Kaladharan; Palaniyappan Subramanian; Rafia Akhtar; Senthil Kumar Thiruppathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Corrigendum to “Investigation of electrochemical performance of an efficient Ti2O3–CeO2 nanocomposite for enhanced pollution-free energy conversion applications” [J. Environ. Manage. 295 (2021) 113138] - S. Swathi; R. Yuvakkumar; P. Senthil Kumar; G. Ravi; Dhayalan Velauthapillai (Journal of Environmental Management, 2026)

Corrigendum to “Optimisation of anaerobic digestion of palm oil mill effluent with biochar addition: Synergistic application of Artificial neural network and response Surface Methodology” [Fuel 398 (2025) 135514] - Pui Yan Chang; Yi Jing Chan; Senthil Kumar Arumugasamy; Yoke Kin Wan; Jun Wei Lim (Fuel, 2026)

Crosstalk Between Neuronal and Glial Cells in Diabetic Retinopathy: Mechanisms and Implications for Neurodegeneration - Nidhi Kumari; Shubhrajit Barman; Senthil Kumar Ganesan (Molecular Neurobiology, 2026)

Genome wide identification, characterization and evolutionary relationship analysis of the Dof gene family in Drumstick plant (Moringa oleifera) - Senthil Kumar Avinash; Malarvizhi Mathiazhagan; Dayanandhi Elangovan; Hara Gopal Krishnajee; Pooja Bharti; Raja Shankar; Laxman R. Hunashikatti; Kundapura V. Ravishankar (Genetic Resources and Crop Evolution, 2026)

Climate-driven habitat suitability and adaptation planning for endangered elephants (Loxodonta africana and Loxodonta cyclotis) - Narayanan Natarajan; Senthil Kumar Dineshkumar; S. Syed Masoodhu; Mangottiri Vasudevan (Landscape and Ecological Engineering, 2026)

Retraction notice to “Investigation of PEG directed Sb2WO6 for dyes removal from wastewater” [Chemosphere 291, Part 1, March 2022, 132677] - S.P. Keerthana; R. Yuvakkumar; P. Senthil Kumar; G. Ravi; S.I. Hong; Dhayalan Velauthapillai (Chemosphere, 2025)

Engineering MOF-derived CuMn2O4/CuMnO2 heterojunctions for efficient and durable water-splitting electrocatalysis - Pavithra Suresh; Senthil Pandian Muthu; Anuj Kumar; Mohd Ubaidullah; Abirami Natarajan (Journal of Environmental Chemical Engineering, 2025)

Study of disturbances of human-induced errors on the optimal decisions of smart charging and energy sharing of zero-emission vehicles with quantified traffic congestion impact - Yaxuan Li; Gokula Manikandan Senthil Kumar; Sunliang Cao (Sustainable Cities and Society, 2025)

Mining overburden sand from lignite mines as a partial replacement for fine aggregates in concrete - B. Balakrishna Prasanna; G.R. Senthil Kumar; P. Gopinathan; Amit Karmakar; Md Mustaque Ansari; T. Subramani (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Late Amazonian continual volcanic eruption, contemporaneous tectonics and pit chain formation in the central Tharsis region, Mars: Implications for long-lived magmatism and mantle plume - Vivek Krishnan; P. Senthil Kumar (Icarus, 2025)

Upcycling agro-waste as a physical template for synthesizing self-doped Fe2O3 and CuO nanoparticles: Assessing textile dye and antibiotics degradation efficiency - Varuna Kumaravel; Senthil Kumar Sadasivam; Ishwarya Pownraj; Nivaskanna Ilangovan; K Jagajjanani Rao (Environmental Research, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

Retraction notice to “Annealing temperature effect on cobalt ferrite nanoparticles for photocatalytic degradation” [Chemosphere 281, October 2021, 130903] - S. Swathi; R. Yuvakkumar; P. Senthil Kumar; G. Ravi; Dhayalan Velauthapillai (Chemosphere, 2025)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Optimisation of anaerobic digestion of palm oil mill effluent with biochar addition: Synergistic application of Artificial neural network and response Surface Methodology - Pui Yan Chang; Yi Jing Chan; Senthil Kumar Arumugasamy; Yoke Kin Wan; Jun Wei Lim (Fuel, 2025)

Retraction notice to “Deep insights into kinetics, optimization and thermodynamic estimates of methylene blue adsorption from aqueous solution onto coffee husk (Coffee arabica) activated carbon” [Environ. Res. 236-P2 (2023) 116735] - Prabu Deivasigamani; P. Senthil Kumar; Sathish Sundaraman; Michael Rahul Soosai; A. Annam Renita; Karthikeyan M; Nessipkhan Bektenov; Omirserik Baigenzhenov; Venkatesan D; Aravind Kumar J (Environmental Research, 2025)

Ultra-low voltage hydrazine splitting with pulsed laser harnessed Ir/CoP for efficient Zn-hydrazine battery systems - Ramar Govindasamy; Cheol Joo Moon; Raja Arumugam Senthil; Velusamy Maheskumar; Anuj Kumar; Seongbo Lee; Mohd Ubaidullah; Myong Yong Choi (Chemical Engineering Journal, 2025)

Design, synthesis and evaluation of benzothiazole-derived phenyl thioacetamides as dual inhibitors of monoamine oxidases and cholinesterases - Sandeep Kumar; Rangan Mitra; Senthil Raja Ayyannan (Molecular Diversity, 2025)

Photocatalytic reduction of Cr (VI) ions using eggshells/graphitic carbon nitride composite - J. Ambigadevi; P. Senthil Kumar; B. Chitra; G. Rangasamy (International Journal of Environmental Science and Technology, 2025)

Electrochemical Sensing of Sulfamethoxazole Antibiotic in Water at Graphene Oxide/Zinc Oxide Nanocomposites Modified Glassy-Carbon Electrode: Optimization and Real Time Measurement - Senthil Rathi Balasubramani; Senthil Kumar Ponnusamy; Nethaji Pavadai; Senthil Theerthagiri (International Journal of Environmental Research, 2025)

Investigating the immunomodulatory and haemato-protective roles of curry leaf ethanolic extract (Murraya koenigii) in Labeo rohita fingerlings Infected with Aeromonas hydrophila - Sourabh Debbarma; Bagthasingh Chrisolite; Panchavarnam Sivasankar; P. Senthil Kumar; V. Senthil Kumar; N. Daniel; Palaniappan Subash; Muthumariappan Selvamagheswaran; Mohamed Mansoor; Magesh Kumar Paulraj (Fish Physiology and Biochemistry, 2025)

The Role of Business Strategy in Advancing Sustainability Goals: a Comprehensive Systematic and Bibliometric Analysis - Senthil Kumar Jaya Prakash; Ravi Aluvala; Srinivasa Rao Y; Kusuma Thimmapuram; Srihari G (Circular Economy and Sustainability, 2025)

Green synthesis of silver nanoparticles using Ocimum sanctum for efficient Congo red dye removal: a response surface methodology approach - S. Murugeshwari; B. Senthil Rathi; N. Kalaiarasi; R. M. Saravana Kumar; I. Arunkumar; M. Vasanth; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

In-vitro regeneration via direct and indirect organogenesis in Brachystelma glabrum Hook.f. - an endemic species of the Eastern ghats, India - S. Revathi Lakshmi; S. Parthibhan; S. Muthukrishnan; T. Senthil Kumar; M. V. Rao (Vegetos, 2025)

Algae-based nanoparticles for enhancing sustainable applications in integrated food-water ecosystem - Suman Nayak; Bunushree Behera; Kungkamliu Newmei; Mari Selvam S.; Vanish Kumar; Esther Lalnunmawii; Nachimuthu Senthil Kumar; Bhaskar Das; Lavanyasri Rathinavel (Journal of Environmental Management, 2025)

Self-assembly of binder-free 3D NiMoO4/ZnCo-LDH/NF core/shell architecture for efficient oxygen evolution reaction - Moorthy Krishnamachari; Mohanraj Kumar; Muthu Senthil Pandian; Paranthaman Vijayakumar; Jih-Hsing Chang (Fuel, 2025)

Polyethylene microplastics induce behavioural and developmental deficits in the Drosophila model - Sharine Priscilla; Ryo Nagasawa; Swetha Senthil Kumar; Sai Charan Kasavaraju; Chirayu Chandrakanth; Premkumar Sivakumar; Hamsini Bharat; Iyeswaran Muthulingam; Masakazu Umezawa; Sahabudeen Sheik Mohideen (Toxicology and Environmental Health Sciences, 2025)
Introduction Polyethylene (PE) is a common plastic used in a variety of applications such as bottles, carry bags, and packaging materials. The extensive use and improper disposal of PE MPs have severe environmental impacts. PE MPs infiltrate ecosystems via wastewater discharge and landfill runoff, getting consumed by organisms and causing harmful bioaccumulation. These microplastics also absorb toxins and transport them up the food chain, posing health risks to humans. Objectives and methods We generated PE MPs with sizes between 2 and 10 μm and assessed their toxicity on the Drosophila model. The study included an evaluation of the survival patterns of adult flies and behavioural and biochemical parameters in larvae and adults. Results Our in vivo toxicological assessment revealed a severe decline in the longevity of flies and locomotory function in the larvae and adults. In addition, we also noticed a decrease in the fly eclosion rate and a substantial increase in the antioxidant enzyme activity. This result was further supported by the alterations observed in the transcriptional activation of stress response genes like Hsp70Bc , rpr , cat , p53 and sod . Conclusion The findings from the study reveal perspectives on the harmful impacts of PE MPs on flies’ growth and development, as well as the rising threat to our environment posed by these microplastics. Graphical abstract

Mud volcanoes and microbial communities: Unraveling the mysteries of formation, features, and occurrence - Senthil Kumar Rajendran; Suprokash Koner; Bashir Hussain; Hsin-Chi Tsai; Zeng-Yei Hseu; Jung-Sheng Chen; Shih-Wei Huang; Danish Ali; Muhammad Adil Khan; Bing-Mu Hsu (Journal of Asian Earth Sciences, 2025)

Precise arrangement of cubic cobalt/zinc oxide nanohybrids anchored on rGO nanosheets as an efficient bifunctional electrocatalysts for overall water splitting - Simiyon Denisdon; P. Senthil Kumar; Chitra Boobalan; Gayathri Rangasamy (Fuel, 2025)

Integrated AI and machine learning pipeline identifies novel WEE1 kinase inhibitors for targeted cancer therapy - Jaikanth Chandrasekaran; Dhanushya Gopal; Lokesh Vishwa Sureshkumar; Infant Xavier Santhiyagu; Varsha Senthil Kumar; Bhuvaneshwari Munuswamy; Beevi Fathima Harshatha Mohamed You Gani; Mohit Agrawal (Molecular Diversity, 2025)

Validation of markers linked to the double flower per peduncle trait in Indian chickpea cultivars and germplasm: genetic variation in SFL and other R2R3-MYB transcription factors - P. S. Shanmugavadivel; A K. Srivastava; M. Senthil Kumar; Aravind Kumar Konda; Anamika Kushwaha; Jyotirmay Dubey; Shivam Anand; Meenal Rathore; Girish Prasad Dixit (Genetic Resources and Crop Evolution, 2025)

Environmental remediation of malachite green dye from water using hydrothermally carbonized agro-waste biomass: mechanisms and optimization - S. Mahalaxmi; P. Senthil Kumar; B. Chitra; G. Rangasamy (International Journal of Environmental Science and Technology, 2025)

Advances in two-line hybrid rice breeding: leveraging thermosensitive genetic male sterility system in rice for improved global rice production - Bhavna Baxla; Kalaimagal Thiyagarajan; Manonmani Swaminathan; Anita Bellie; Sritharan Natarajan; Senthil Kumar Govindan (Euphytica, 2025)

Utilization of charnockite rock as manufactured-aggregate for construction industry: a case study from Thiruvakkarai quarry and M-sand plant in Tamil Nadu, India - B. Balakrishna Prasanna; G. R. Senthil Kumar; T. Subramani; Ramamohana Reddy Bellum (Environmental Geochemistry and Health, 2025)

Recent progress in nanocellulose-based biocomposites for bone tissue engineering and wound healing applications - V. Parthasarathy; P. Senthil Kumar; Annie Aureen Albert; Senthilkumar Krishnasamy; M. Chandrasekar (Carbohydrate Polymers, 2025)

Nitrate pollution index and age wise health risk appraisal for the Pambar River basin in south India - C. N. Sridhar; T. Subramani; G. R. Senthil Kumar; K. Soundaranayaki (Environmental Geochemistry and Health, 2025)

Retraction notice to “Current advances in microbial fuel cell technology toward removal of organic contaminants – A review” [Chemosphere 287, Part 2, January 2022, 132186] - R. Suresh; Saravanan Rajendran; P. Senthil Kumar; Kingshuk Dutta; Dai-Viet N. Vo (Chemosphere, 2025)

Engineering properties of hydrochar fabricated from hydrothermal carbonization of lignocellulosic biomass: Practice as adsorbent and catalyst in water treatment - G. Prasannamedha; P. Senthil Kumar; Senthil Rathi Balasubramani; V. Parthasarathy; A. Daril Deehen; E. Jananie; V. Lokesh; S. Shivani; S. Keerthana; I. Shivani; Gayathri Rangasamy (Journal of Water Process Engineering, 2025)

Exploring quinazoline-derived copper(I) complex coated intravaginal ring against vulvovaginal candidiasis causing Candida species - Dhesiga Krishnan; Sudaarsan Aruna Senthil Kumar; Sowndarya Jothipandiyan; Venkatesan Yamuna Devi; Devarajan Suresh; Paramasivam Nithyanand (Biofouling, 2025)

Retraction notice to “Recent advancements in microbial fuel cells: A review on its electron transfer mechanisms, microbial community, types of substrates and design for bio-electrochemical treatment” [Chemosphere 286 (2022) 131856] - S. Prathiba; P. Senthil Kumar; Dai-Viet N. Vo (Chemosphere, 2025)

Sustainable fuel production from waste ship oil sludge: A comprehensive technical and socio-economic analysis towards zero-waste discharge - K.B. Sasidhar; Somasundaram Murugavelh; Porpatham Ekambaram; Senthil Kumar Arumugam (Process Safety and Environmental Protection, 2025)

‘Nomadic’ Hematopoietic Stem Cells Navigate the Embryonic Landscape - Anand Badhri Narayan; Senthil Kumar Hariom; Ayan Prasad Mukherjee; Deotima Das; Aadhira Nair; Everette Jacob Remington Nelson (Stem Cell Reviews and Reports, 2025)

Remote sensing application in plant protection and its usage in smart agriculture to hasten decision making of the farmers - R. Sathya Priya; N. Jagathjothi; M. Yuvaraj; N. Suganthi; R. Sharmila; M. Saranya; L. Karthiba; P. Murali Arthanari; C. Bharathi; G. Senthil Kumar; Jaiby Cyriac; S. Anandha Krishnaveni (Journal of Plant Diseases and Protection, 2025)

Comprehensive assessment of current municipal solid waste management in Chennai, India: a critical case study with real-time analysis - R. Shiam Babu; K. Prasanna; P. Senthil Kumar; G. Rangasamy (International Journal of Environmental Science and Technology, 2025)

ALR inhibits HBV replication and autophagosome formation by ameliorating HBV-induced ROS production in hepatic cells - Amit Kumar Mishra; Md. Musa Hossain; Teja Naveen Sata; Kishor Pant; Ajay K. Yadav; Amrendra Kumar Sah; Parul Gupta; Md Ismail; Baibaswata Nayak; Shalimar; Senthil Kumar Venugopal (Virus Genes, 2025)

The resurgence of monkeypox clade Ib: a global health emergency and concern - Suresh Kumar; Gunasekaran Subramaniam; K. J. Senthil Kumar (Archives of Virology, 2025)

Exposure and risk assessment of organophosphorus pesticides in brinjal and tomato of Coimbatore District, Tamil Nadu, India - Arun Bala S.; Asha Sathish; K. Nithya; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

Exotic coherent structures and their collisional dynamics in a (3+1) dimensional Bogoyavlensky–Konopelchenko equation - C. Senthil Kumar; R. Radha (Wave Motion, 2025)

First report of Lasiodiplodia iraniensis causing postharvest decay in chillies (Capsicum spp.) - Rafia Akhtar; Senthil Kumar Thiruppathi (Physiological and Molecular Plant Pathology, 2025)

Tailoring spinel cobalt-oxide geometry for ultrahigh sensitive nonenzymatic electrocatalytic oxidation and sensing of glucose in batch injection analysis - Yesudas K Yashly; Sathesh P Sreeshma; Saravana Kumar Tharinidevi; Gopal Buvaneswari; Annamalai Senthil Kumar (Chemical Engineering Journal, 2025)

Exploring rice genotypes for nitrogen use efficiency under different nitrogen regimes - Sritharan Natarajan; Krishna Surendar Karuppasamy; Anitha Ramasamy; Tamilselvi Chellamuthu; Nithila Sadasivam; Boomiraj Kovilpillai; Senthil Kumar Govindan; Ravichandran Veerasamy; Raveendran Muthurajan (Plant Physiology Reports, 2025)

AgriDrones: A Holistic Review on the Integration of Drones in Indian Agriculture - Vishwajeet Ramesh Avhale; G. Senthil Kumar; R. Kumaraperumal; G. Prabukumar; C. Bharathi; R. Sathya Priya; M. Yuvaraj; D. Muthumanickam; P. Parasuraman; S. Pazhanivelan (Agricultural Research, 2025)

Retraction notice to “Recent advancements of spinel ferrite based binary nanocomposite photocatalysts in wastewater treatment”[Chemosphere 274 (2021) 129734] - R. Suresh; Saravanan Rajendran; P. Senthil Kumar; Dai-Viet N. Vo; Lorena Cornejo-Ponce (Chemosphere, 2025)

Retraction notice to “A fuzzy cognitive map approach to predict the hazardous effects of malathion to environment (air, water and soil)” [Chemosphere 263 (2021) 127926] - S. Poomagal; R. Sujatha; P. Senthil Kumar; Dai-Viet N. Vo (Chemosphere, 2025)

Retraction notice to “Enhancement of lipid accumulation in microalga Desmodesmus sp. VV2: Response surface methodology and artificial neural network modeling for biodiesel production” [Chemosphere 293 (2022) 133477] - Elamathi Vimali; Arumugasamy Senthil Kumar; Nagamalai Sakthi Vignesh; Balasubramaniem Ashokkumar; Amarajothi Dhakshinamoorthy; Aswathy Udayan; Muthu Arumugam; Arivalagan Pugazhendhi; Perumal Varalakshmi (Chemosphere, 2025)

Retraction notice to “Adsorptive removal of Pb(II) ions onto surface modified adsorbents derived from Cassia fistula seeds: Optimization and modelling study” [Chemosphere 283 (2021) 131276] - R.V. Hemavathy; A. Saravanan; P. Senthil Kumar; Dai-Viet N. Vo; S. Karishma; S. Jeevanantham (Chemosphere, 2025)

Phytosociology and habitat suitability studies on Endemic jewel Orchid Aenhenrya rotundifolia in Southern Western Ghats, India - Subramanian Palaniyappan; Gopalakrishnan Aazhivaendhan; Rajendran Silambarasan; Noyaljohnson Tinoammini; Chinnaiyan Rajasekar; Thiruppathi Senthil Kumar (Vegetos, 2025)

Artificial intelligence integration in conventional wastewater treatment techniques: techno-economic evaluation, recent progress and its future direction - B. Senthil Rathi; P. Senthil Kumar; S. Sanjay; M. Prem Kumar; Gayathri Rangasamy (International Journal of Environmental Science and Technology, 2025)

Impact of Sensitizer Yb3+ on Structural and Optical Properties of AE2SiO4 (AE = Ba, Ca, Sr) Orthosilicates - Aastha Sahu; Nand Kumar Shante; Jai Singh; K. Senthil Kannan; R. P. Patel (Journal of Fluorescence, 2024)

Trust evaluation model in IoT environment: a review - Senthil Kumar Chandrasekaran; Vijay Anand Rajasekaran (Environment, Development and Sustainability, 2024)

Surface modification of Au nanoparticles with porous carbon microsheets/Bi2S3 for enhanced electrochemical monitoring of hazardous sulfamethoxazole - Raja Nehru; Balamurugan Senthil Kumar; Chiu-Wen Chen; Cheng-Di Dong (Journal of Environmental Chemical Engineering, 2024)

Enhancing ammonia decomposition in ammonium hydroxide/diesel emulsion through hybrid nanocomposite and optimization for improved and greener combustion - Shanmugavel Kuppusamy; Senthil Kumar Duraisamy; Suresh Vellaiyan (Fuel, 2024)

Insights into dual-functional catalytic activity of laser-driven CoGaIr-LDH nanosheets in water electrolysis for green hydrogen production via in-situ Raman and theoretical analyses - Akash Prabhu Sundar Rajan; Raja Arumugam Senthil; Cheol Joo Moon; Anuj Kumar; Ahreum Min; Mohd Ubaidullah; Myong Yong Choi (Chemical Engineering Journal, 2024)

Significance of Viable But Non-culturable (VBNC) State in Vibrios and Other Pathogenic Bacteria: Induction, Detection and the Role of Resuscitation Promoting Factors (Rpf) - Rakshana Balagurusamy; Lekha Gopi; Dhivya Shre Senthil Kumar; Kamalalakshmi Viswanathan; Velmurugan Meganathan; Karuppanan Sathiyamurthy; Baskaran Athmanathan (Current Microbiology, 2024)

Cell-free supernatants of probiotic consortia impede hyphal formation and disperse biofilms of vulvovaginal candidiasis causing Candida in an ex-vivo model - Sudaarsan Aruna Senthil Kumar; Dhesiga Krishnan; Sowndarya Jothipandiyan; Ramyadevi Durai; B. Narayanan Vedha Hari; Paramasivam Nithyanand (Antonie van Leeuwenhoek, 2024)

Unmasking complexities of combined stresses for creating climate-smart crops - Prachi Pandey; Muthappa Senthil-Kumar (Trends in Plant Science, 2024)

Fabrication and characterization of poly(methyl vinyl ether maleic anhydride) blended poly(lactic acid) ultrafiltration membrane with upgraded antifouling and separation performance - Jenet George; Vahulabaranan Rajagopalan; P. Senthil Kumar; Maheswari Purushothaman; Panneerselvam Perumal; Vinoth Kumar Vaidyanathan; Gayathri Rangasamy (Process Safety and Environmental Protection, 2024)

Exploring chemically and physically modified plant-based fiber biomass for biosorption in wastewater treatment: A concise review - N. Rashmi; S.A. Salmataj; P. Senthil Kumar; Pushpanjali Bhat (Journal of Water Process Engineering, 2024)

Design of biocompatible gelatin hydrogels reinforced with magnetite nanoparticles: Effective removal of chromium from water environment - P.S. Anulekshmi; K. Nithya; P. Senthil Kumar; Asha Sathish; Priyadarshini M; E. Rekha; Aswathy S. Cheruvally; Gayathri Rangasamy (Environmental Research, 2024)

Spatiotemporal performance evaluation of high-resolution multiple satellite and reanalysis precipitation products over the semiarid region of India - Elangovan Devadarshini; Kulanthaivelu Bhuvaneswari; Shanmugam Mohan Kumar; Vellingiri Geethalakshmi; Manickam Dhasarathan; Alagarsamy Senthil; Kandasamy Senthilraja; Shahbaz Mushtaq; Thong Nguyen-Huy; Thanh Mai; Louis Kouadio (Environmental Monitoring and Assessment, 2024)

Exploring the anticandidal potential: Evaluating leaf extract efficacy and GC–MS metabolite profiling of Chenopodium album var. album L. - Subiya Showkat; Thiruppathi Senthil Kumar (South African Journal of Botany, 2024)

An effective in vitro propagation of Coelogyne mossiae Rolfe: An endangered endemic orchid of Western Ghats, India - Shivakrishnan Kaladharan; Muthukumar Mariappan; Senthil Kumar Thiruppathi (South African Journal of Botany, 2024)

Optimal design of an inclined barrier for performance improvement of an oscillating water column device with an artificial neural network model - Senthil Kumar Natarajan; Arun George; Il Hyoung Cho (Ocean Engineering, 2024)

Crustal origin for olivine in the lunar Shioli crater ejecta boulders: Insights from the geological setting of Theophilus crater and Nectaris basin - P. Senthil Kumar; Abhisek Mishra; Vivek Krishnan; Netra S. Pillai; Sumit Pathak; Sriram S. Bhiravarasu; Shyama Narendranath; K. Jaya Prasanna Lakshmi; Satadru Bhattacharya (Icarus, 2024)

Design, synthesis and evaluation of sesamol-derived acetamides as dual inhibitors of monoamine oxidases and cholinesterases - Sandeep Kumar; Rangan Mitra; Senthil Raja Ayyannan (Medicinal Chemistry Research, 2024)

Correction to: Experimental study of the thermal performance of heat storage–integrated solar receiver for parabolic dish collectors - Senthil Kumar Vishnu; Ramalingam Senthil (Environmental Science and Pollution Research, 2024)

Strategies of entomopathogenic nematodes and their symbiotic bacteria against plant parasitic nematodes - Ketha Sushma; Shanthi A; Anita B; Senthil Kumar P; Shanmugam S. P (Physiological and Molecular Plant Pathology, 2024)

Exploring transition metal hydroxides performance in membrane-free electrolyzer based decoupled water splitting for step-wise production of hydrogen and oxygen - Subramanian Rajalekshmi; Sakkarapalayam Murugesan Senthil Kumar; Alagarsamy Pandikumar (Chemical Engineering Journal, 2024)

Nanoformulations of plant essential oils for managing mycotoxins producing fungi: An overview - Sadia Zafar; Muhammad Farooq Arshad; Husnain Khan; Rushna Menahil; Lamia Iqbal; S. Jaya Prabhavathi; M. Senthil Kumar; Ayman F. Omar; Tayyaba Shaheen (Biocatalysis and Agricultural Biotechnology, 2024)

Navigating towards dry root rot resistance in mungbean: impacts, mechanisms, and management strategies - Nithyananth Hemanth Sadhana; Subramaniam Geethanjali; Rishabh Mirchandani; Senthil Natesan; Muthappa Senthil-Kumar (Plant Physiology Reports, 2024)

Effective removal of chromium by adsorption using Delonix regia bark derived activated carbon from aqueous solution: a sustainable approach - Janet Joshiba Ganesan; Chia-Shang Chang Chien; P. Senthil Kumar; Hemavathi Sundaram; Hariharan Thangappan; Aravindan Achuthan; Sivarethinamohan Rajamanickam; Gayathri Rangasamy (Environmental Geochemistry and Health, 2024)

Samarium-doped vanadium pentoxide nanorods anchored reduced graphene oxide nanocomposite as a bi-functional electrode material for supercapacitor and direct methanol oxidation fuel cell applications - V. Uma Shankar; Yuttana Mona; P. Suganya; P. Senthil Kumar; D. Govindarajan; V. Mangla Gowri; E. Narayanamoorthi; Pei-Chien Tsai; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Process Safety and Environmental Protection, 2024)

Preparation and characterization of activated carbon from corn cob by chemical activation and their adsorption of brilliant green dye from wastewater - Sakthivel Kumaravel; M. Geetha; Theophile Niyitanga; D. Senthil Kumar; Mysoon M. Al-Ansari; R. Mythili; Sanjeevamuthu Suganthi; L. Guganathan; A. Murugan; S. Ragupathy (Process Safety and Environmental Protection, 2024)

Cardiovascular adaptations in microgravity conditions - Senthil Kumar Hariom; Everette Jacob Remington Nelson (Life Sciences in Space Research, 2024)

Exploring the Link Between Seismic and Atmospheric Parameters Using Spatio Temporal Analysis: Implications for Earthquake Forecasting - M. Senthil Kumar; N. Venkatanathan (Pure and Applied Geophysics, 2024)

A critical review on biochar for the removal of toxic pollutants from water environment - R. Sivaranjanee; P. Senthil Kumar; B. Chitra; Gayathri Rangasamy (Chemosphere, 2024)

A review on recent advancements in the treatment of polyaromatic hydrocarbons (PAHs) using sulfate radicals based advanced oxidation process - Fetcia Jackulin; P. Senthil Kumar; B. Chitra; S. Karthick; Gayathri Rangasamy (Environmental Research, 2024)

Correction: Association of Biochemical Parameters and Screening for Mutations in the MCU Gene in Alzheimer’s Disease Patients - Anila Venugopal; Mahalaxmi Iyer; Arul Narayanasamy; T. Ravimanickam; Abilash Valsala Gopalakrishnan; Mukesh Kumar Yadav; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2024)

Genetic Instability and Disease Progression of Indian Rett Syndrome Patients - Mohan Gomathi; Venkatesan Dhivya; Vijayakumar Padmavathi; Murugasamy Pradeepkumar; S. Robert Wilson; Nachimuthu Senthil Kumar; Vellingiri Balachandar (Molecular Neurobiology, 2024)

Association of Biochemical Parameters and Screening for Mutations in the MCU Gene in Alzheimer’s Disease Patients - Anila Venugopal; Mahalaxmi Iyer; Arul Narayanasamy; T Ravimanickam; Abilash Valsala Gopalakrishnan; Mukesh Kumar Yadav; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2024)

Association Study Between Kynurenine 3-Monooxygenase (KMO) Gene and Parkinson’s Disease Patients - Harysh Winster Suresh Babu; Ajay Elangovan; Mahalaxmi Iyer; Laxmi Kirola; Sureshan Muthusamy; Priyanka Jeeth; Sindduja Muthukumar; Harvey Vanlalpeka; Abilash Valsala Gopalakrishnan; Saraboji Kadhirvel; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2024)

Novel antifungal compound from Prunella vulgaris: An in-silico approach towards the discovery of potent inhibitor to combat phytopathogenic fungi - Rafia Akhtar; Dhanasekaran Dharumadurai; Thiruppathi Senthil Kumar (Biocatalysis and Agricultural Biotechnology, 2024)

Enhancement of grain yield in rice under combined drought and high-temperature stress conditions by maintaining photosynthesis through antioxidant enzyme activities by melatonin - Arun Kumar Kathirvel; Kalarani M. Karuppasami; Vijayalakshmi Dhashnamurthi; Geethalakshmi Vellingiri; Raveendran Muthurajan; Anandhi Venugopal; Anitha Kuppusamy; Senthil Alagarsamy (Plant Physiology Reports, 2024)

Multi-perspective Investigations of Aerosol’s Non-linear Impact on Unmanned Aerial Vehicle for Air Pollution Control Applications Under Various Aerosol Working Environments - Gopinath Vinayagam; Ragavendra Thaiyan Rajendran; Mahima Swetha Mohan; Beena Stanislaus Arputharaj; Shyam Sundar Jayakumar; Sundhar Baskar; Parvathy Rajendran; Raj Kumar Gnanasekaran; Senthil Kumar Madasamy; Vijayanandh Raja (Aerosol Science and Engineering, 2024)

Computation of embodied energy and carbon dioxide emissions of geopolymer concrete in high-rise buildings: a case study in Chennai city - Kiruthika K.; Ambily P.S.; Ponmalar V.; Senthil Kumar Kaliyavaradhan (European Journal of Environmental and Civil Engineering, 2024)

Zinc solubilization and organic acid production by the entomopathogenic fungus, Metarhizium pingshaense sheds light on its key ecological role in the environment - C.M. Senthil Kumar; Sharon D'Silva; R. Praveena; Anees Kaprakkaden; L.R. Athira Krishnan; M. Balaji Rajkumar; V. Srinivasan; R. Dinesh (Science of The Total Environment, 2024)

Membrane-based removal of fluoride from groundwater - B. Senthil Rathi; P. Senthil Kumar; Gayathri Rangasamy; Michael Badawi; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2024)

A sustainable redox-active electrocatalyst utilizing natural quercetin-infused MWCNT for ultra-sensitive detection of environmental Cr(VI) contaminants - Sugumar Monisha; Annamalai Senthil Kumar (Chemical Engineering Journal, 2024)

In vitro asymbiotic seed germination and micropropagation of Dendrobium heyneanum Lindl. – an endemic orchid of Western Ghats, India - Shivakrishnan Kaladharan; Anbazhakan Rengasamy; Rajasekar Chinnaiyan; Muthukumar Mariappan; Senthil Kumar Thiruppathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Dynamic pricing for load shifting: Reducing electric vehicle charging impacts on the grid through machine learning-based demand response - Balakumar Palaniyappan; Senthil Kumar R; Vinopraba T (Sustainable Cities and Society, 2024)

Polypyrrole-carbon black/BiPO4 composites as efficient electrocatalysts for sensitive detection of furazolidone: A cost-effective approach for environmental monitoring - Raja Nehru; Srikanth Gnanakrishnan; Balamurugan Senthil Kumar; Chiu-Wen Chen; Cheng-Di Dong (Process Safety and Environmental Protection, 2024)

Hydrogen generation by heterogeneous catalytic steam reforming of short-chain alcohols: a review - Anh Ngoc T. Cao; Kim Hoong Ng; Shams Forruque Ahmed; Ha Tran Nguyen; Ponnusamy Senthil Kumar; Huu-Tuan Tran; Natarajan Rajamohan; Mohammad Yusuf; Pau Loke Show; Akash Balakrishnan; Mahadi B. Bahari; Tan Ji Siang; et al. (Environmental Chemistry Letters, 2024)

Design and Characterization of Anticancer Peptides Derived from Snake Venom Metalloproteinase Library - S. Saranya; M. Bharathi; N. Senthil Kumar; P Chellapandi (International Journal of Peptide Research and Therapeutics, 2024)

Green synthesis of carbon quantum dots from teak leaves biomass for in situ precipitation and regenerative-removal of methylene blue-dye - Zakriya Waseem Basha; Annamalai Senthil Kumar; Sarangapani Muniraj (Environmental Science and Pollution Research, 2024)

Invitro germination and optimization of basal media for protocorm-like bodies proliferation in Dienia ophrydis (J. Koenig) Seidenf - Noyaljohnson Tinoammini; Gopalakrishnan Aazhivaendhan; Thiruppathi Senthil Kumar (Rhizosphere, 2024)

Fluorescence enhancing and quenching signal based on new approach for selective detection of multiple organochlorine pesticides using blue emissive-carbon dot - P. Nethaji; P. Revathi; P. Senthil Kumar; M. Logesh; Jothi Ramalingam Rajabathar; H.A. Al-Lohedan; S. Arokiyaraj; Gayathri Rangasamy (Environmental Pollution, 2024)

Phyto-nano-MgO quantum dots by ultrasonic formulation for evaluation of toxin In-Vivo/Vitro/Silico sequels - S. Sreevidya; Sushma Yadav; Sunita Sanwaria; Yokraj Katre; Anil Kotasthane; R. Senthil Kumar; Ajaya Kumar Singh; Md. Abu Bin Hasan Susan (Chemical Engineering Journal, 2024)

Stress combinations and their interactions in crop plants - Venkategowda Ramegowda; Alagarswamy Senthil; Muthappa Senthil-Kumar (Plant Physiology Reports, 2024)

Chlamydomonas as a model system for studying the relevance of plant genes for their involvement in multiple individual and combined stresses: a study unravelling PgCuZnSOD and PgAPX gene functions - H. M. Mamrutha; Geetha Govind; Hema Ramanna; Radha Sivarajan Sajeevan; A. N. Lokesha; Muthappa Senthil-Kumar; Karaba N. Nataraja (Plant Physiology Reports, 2024)

Plant responses to concurrent abiotic and biotic stress: unravelling physiological and morphological mechanisms - Shikha Dixit; Palaiyur Nanjappan Sivalingam; R. K. Murali Baskaran; Muthappa Senthil-Kumar; Probir Kumar Ghosh (Plant Physiology Reports, 2024)

Impacts of combined drought and high-temperature stress on growth, physiology, and yield of crops - K. A. Mumithra Kamatchi; K. Anitha; K. Arun Kumar; A. Senthil; M. K. Kalarani; M. Djanaguiraman (Plant Physiology Reports, 2024)

Abiotic stress impact on the interaction between Macrophomina phaseolina and crop plants - Shubhashish Ranjan; Rishabh Mirchandani; Muthappa Senthil-Kumar (Plant Physiology Reports, 2024)

Machine learning methods for the modelling and optimisation of biogas production from anaerobic digestion: a review - Jordan Yao Xing Ling; Yi Jing Chan; Jia Win Chen; Daniel Jia Sheng Chong; Angelina Lin Li Tan; Senthil Kumar Arumugasamy; Phei Li Lau (Environmental Science and Pollution Research, 2024)

Fungal bioremediation approaches for the removal of toxic pollutants: Mechanistic understanding for biorefinery applications - Bala Krishnan Navina; Nandha Kumar Velmurugan; P. Senthil Kumar; Gayathri Rangasamy; Jeyanthi Palanivelu; P. Thamarai; A.S. Vickram; A. Saravanan; Awais Shakoor (Chemosphere, 2024)

Interface engineering of heterogeneous NiMn layered double hydroxide/vertically aligned NiCo2S4 nanosheet as highly efficient hybrid electrocatalyst for overall seawater splitting - S. Gopalakrishnan; G. Anandha babu; S. Harish; E. Senthil Kumar; M. Navaneethan (Chemosphere, 2024)

A highly sensitive electrochemical sensor for Cr6+ ions detection using Ag NPs/rGO/quercetin modified glassy carbon electrode for water applications - G. Surendra Rajkumar; P. Senthil Kumar; Gayathri Rangasamy (Groundwater for Sustainable Development, 2024)

A review on recent technological breakthroughs in anaerobic digestion of organic biowaste for biogas generation: Challenges towards sustainable development goals - K. Archana; A.S. Visckram; P. Senthil Kumar; S. Manikandan; A. Saravanan; L. Natrayan (Fuel, 2024)

Immobilization of hydrochar in cellulose beads for eradicating paracetamol from synthetic and sewage water - P. Senthil Kumar; M. Shanmugapriya; G. Prasannamedha; Gayathri Rangasamy (Environmental Pollution, 2024)

Top challenges to widespread 3D concrete printing (3DCP) adoption – A review - P.S. Ambily; Senthil Kumar Kaliyavaradhan; Neeraja Rajendran (European Journal of Environmental and Civil Engineering, 2024)

Conversion of seaweed waste to biochar for the removal of heavy metal ions from aqueous solution: A sustainable method to address eutrophication problem in water bodies - Gokulan Ravindiran; Sivarethinamohan Rajamanickam; Muralikrishnan Ramalingam; Gasim Hayder; Balamurugan Karupaiya Sathaiah; Madhava Krishna Reddy Gaddam; Senthil Kumar Muniasamy; Priya Arunkumar (Environmental Research, 2024)

Influencing factors and environmental feasibility analysis of agricultural waste preprocessing routes towards biofuel production – A review - Selvakumar Periyasamy; Adane Asefa Adego; P. Senthil Kumar; G.G. Desta; T. Zelalem; V. Karthik; J. Beula Isabel; Mani Jayakumar; Venkatesa Prabhu Sundramurthy; Gayathri Rangasamy (Biomass and Bioenergy, 2024)

Callus induction and efficient in vitro plant regeneration protocol for Chickpea - Vinod Kumar Jangid; Muthappa Senthil-Kumar; Divya Chandran; Senjuti Sinharoy (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

Meteorological impact on the incidence of COVID-19 and SARS-CoV-2 variants in Mizoram, Northeast India - Rita Zomuanpuii; Pa Chuau Lalrohlua; Benjamin Lalbiakmawia; Zohmangaiha Chawngthu; Lalmuansangi Hmar; Swagnik Roy; Gracy Laldinmawii; John Zohmingthanga; Nachimuthu Senthil Kumar; John Zothanzama; Henry Zodinliana Pachuau; Aldrin Malsawmtluanga (Environmental Sustainability, 2023)

Impact of air pollutants on climate change and prediction of air quality index using machine learning models - Gokulan Ravindiran; Sivarethinamohan Rajamanickam; Karthick Kanagarathinam; Gasim Hayder; Gorti Janardhan; Priya Arunkumar; Sivakumar Arunachalam; Abeer A. AlObaid; Ismail Warad; Senthil Kumar Muniasamy (Environmental Research, 2023)

Impact of climate change and anthropogenic activities on aquatic ecosystem – A review - Priya A. K; Muruganandam M; Sivarethinamohan Rajamanickam; Sujatha Sivarethinamohan; Madhava Krishna Reddy Gaddam; Priya Velusamy; Gomathi R; Gokulan Ravindiran; Thirumala Rao Gurugubelli; Senthil Kumar Muniasamy (Environmental Research, 2023)

Recent insights into mechanism of modified bio-adsorbents for the remediation of environmental pollutants - A. Saravanan; S. Karishma; P. Senthil Kumar; P. Thamarai; P.R. Yaashikaa (Environmental Pollution, 2023)

Dry root rot disease: Current status and future implications for chickpea production - Rishabh Mirchandani; Vadivelmurugan Irulappan; Aswin Reddy Chilakala; Muthappa Senthil-Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Exploration of a library of piperonylic acid-derived hydrazones possessing variable aryl functionalities as potent dual cholinesterase and monoamine oxidase inhibitors - V. Pavan Kumar; M. S. Vishnu; Sandeep Kumar; Shivani Jaiswal; Senthil Raja Ayyannan (Molecular Diversity, 2023)

Assessment of tRNAThr and tRNAGln Variants and Mitochondrial Functionality in Parkinson’s Disease (PD) Patients of Tamil Nadu Population - Dhivya Venkatesan; Mahalaxmi Iyer; Neethu Raj; Abilash Valsala Gopalakrishnan; Arul Narayanasamy; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Journal of Molecular Neuroscience, 2023)

Strategies for safe management of hospital wastewater during the COVID-19 pandemic - A. Balakrishnan; M. M. Jacob; P. Senthil Kumar; A. Kapoor; M. Ponnuchamy; P. Sivaraman; M. Sillanpää (International Journal of Environmental Science and Technology, 2023)

Polyol synthesis of one-dimensional Ag nanowires for the photocatalytic degradation of textile dye and effective removal of microbes - Senthilnathan Selvaraj; Pamula Balaji Bhargav; Varuna Kumaravel; Senthil Kumar Sadasivam; Balaji Chandra (Environmental Science and Pollution Research, 2023)

Evidence for trail forming ejecta boulder falls around fresh simple impact craters at the lunar Orientale multi-ring basin and implications for ballistic ejecta sedimentation on the Moon - Rupali Mohanty; P. Senthil Kumar; K. Jaya Prasanna Lakshmi; Vivek Krishnan; Abhisek Mishra; G. Sree Sai Karthik (Icarus, 2023)

A comprehensive review on current trends and development of biomethane production from food waste: Circular economy and techno economic analysis - M. Keerthana Devi; S. Manikandan; P. Senthil Kumar; P.R. Yaashikaa; M. Oviyapriya; Gayathri Rangasamy (Fuel, 2023)

Recent advances in edible coatings and their application in food packaging - P.R. Yaashikaa; R. Kamalesh; P. Senthil Kumar; A. Saravanan; K. Vijayasri; Gayathri Rangasamy (Food Research International, 2023)

RETRACTED: Deep insights into kinetics, optimization and thermodynamic estimates of methylene blue adsorption from aqueous solution onto coffee husk (Coffee arabica) activated carbon - Prabu Deivasigamani; P. Senthil Kumar; Sathish Sundaraman; Michael Rahul Soosai; A. Annam Renita; Karthikeyan M; Nessipkhan Bektenov; Omirserik Baigenzhenov; Venkatesan D; Aravind Kumar J (Environmental Research, 2023)

A comprehensive review on immobilized microbes - biochar and their environmental remediation: Mechanism, challenges and future perspectives - A. Saravanan; Pavithra Swaminaathan; P. Senthil Kumar; P.R. Yaashikaa; R. Kamalesh; Gayathri Rangasamy (Environmental Research, 2023)

Corrigendum to “Gold nanoclusters supported Molybdenum diselenide-porous carbon composite as an efficient electrocatalyst for selective ultrafast probing of chlorpyrifos-pesticide” [Chem. Eng. J. 472(2023) 145048] - A.T. Ezhil Vilian; Ali Mohammadi; Soobin Han; Jitendra N. Tiwari; Krishan Kumar; Annamalai Senthil Kumar; Adhimoorthy Saravanan; Yun Suk Huh; Young-Kyu Han (Chemical Engineering Journal, 2023)

Overexpression of OsHsp 18.0 in rice enhanced tolerance to heavy metal stress - Tong-Seung Tseng; Senthil Kumar Rajendran; Yi-Hsin Liu; Shaw-Jye Wu; Chung-An Lu; Ching-Hui Yeh (Plant Cell Reports, 2023)

Hybrid optimization technique-based maximum power point tracking for single-stage grid-connected PV systems - A. T. Sankara Subramanian; M. Senthil Kumar (Clean Technologies and Environmental Policy, 2023)

Acaricidal potential and phytochemical evaluation of ethanolic extract of Argemone mexicana against Rhipicephalus microplus - Manas Kumar Dalei; Manaswini Dehuri; Bijayendranath Mohanty; Dilipkumar Karna; Santwana Palai; Senthil Kuppusamy (International Journal of Tropical Insect Science, 2023)

An efficient electrochemical degradation of toxic pollutants in wastewater using BiOBr/BiVO4 hierarchical structured electrode material - V. Uma Shankar; Abdullah K. Alanazi; P. Senthil Kumar; Jnanesh Anand; G. Prasannamedha; Hala M. Abo-Dief; Gayathri Rangasamy (Chemosphere, 2023)

Emerging aspects of metal ions-doped zinc oxide photocatalysts in degradation of organic dyes and pharmaceutical pollutants – A review - A. Annam Renita; S. Sathish; P. Senthil Kumar; D. Prabu; N. Manikandan; A. Mohamed Iqbal; G. Rajesh; Gayathri Rangasamy (Journal of Environmental Management, 2023)

An integrated approach to the sustainable development and production of biofuel from biopolymers and algal biomass derived from wastewater - A.S. Vickram; A. Saravanan; P. Senthil Kumar; P. Thamarai; S. Yasodha; G. Jamuna; Gayathri Rangasamy (Fuel, 2023)

A critical review on the removal of toxic pollutants from contaminated water using magnetic hybrids - Anbalagan Saravanan; Yaashikaa Ponnambalam Ragini; Ponnusamy Senthil Kumar; Packiyam Thamarai; Gayathri Rangasamy (Environmental Science and Pollution Research, 2023)

Two-step fabrication of cellulose embedded Fe3O4/Fe3+ composite beads as catalyst in degradation of sulfamethoxazole in floating bed reactor - Abdullah K. Alanazi; P. Senthil Kumar; M. Shanmugapriya; G. Prasannamedha; Hala M. Abo-Dief (Chemosphere, 2023)

A novel encapsulation of 16 polycyclic aromatic hydrocarbons in petroleum sludge with palm oil fuel ash binder; an optimization study and sensitivity analysis using machine learning application - Noor Faiza Roslee; Nor Amani Filzah Mohd Kamil; Salina Alias; P. Senthil Kumar; Sadeq Alkhadher; Govarthanan Muthusamy; Adel Al-Gheethi (Chemosphere, 2023)

Bifunctional electrode of bismuth tungsten for electrochemical sensing applications - Abdullah K. Alanazi; P. Senthil Kumar; M. Ramya; Hala M. Abo-Dief; Gayathri Rangasamy (Chemosphere, 2023)

Analysis of blood lead level and its clinical significance among occupational exposed painters in chennai based population: A cross sectional study - Ragunanthanan S; Govardhini Vaiyakkani; Senthil kumar S; Arunkumar Ramachandran; Karthick Rajendran; Narayanasamy Krishnasamy; Priyadarshini Panneerselvam; Jayakrishna Pamarthi; Muthukumaran Rajaram (Journal of Trace Elements in Medicine and Biology, 2023)

An insights of organochlorine pesticides categories, properties, eco-toxicity and new developments in bioremediation process - Femina Carolin C; T. Kamalesh; P. Senthil Kumar; Gayathri Rangasamy (Environmental Pollution, 2023)

Gold nanoclusters supported Molybdenum diselenide-porous carbon composite as an efficient electrocatalyst for selective ultrafast probing of chlorpyrifos-pesticide - A.T. Ezhil Vilian; Ali Mohammadi; Soobin Han; Jitendra N. Tiwari; Krishan Kumar; Annamalai Senthil Kumar; Adhimoorthy Saravanan; Yun Suk Huh; Young-Kyu Han (Chemical Engineering Journal, 2023)

Nano-engineered silver rods from Pleurolobus gangeticus root extract and their antilithiatic and cytoprotective role on oxalate injured renal epithelial cells - Prasobh K. Mohan; T.P. Adarsh Krishna; P.P. Stephy; A. Thirumurugan; T. Senthil Kumar; B.D. Ranjitha Kumari (Biocatalysis and Agricultural Biotechnology, 2023)

A selective analysis of sulfamethoxazole – Trimethoprim in tablet formulations using graphene oxide-zinc oxide quantum dots based nanocomposite modified glassy carbon electrode - P. Senthil Kumar; Padmalaya G; N. Elavarasan; B.S. Sreeja (Chemosphere, 2023)

Laccase-immobilized on superparamagnetic iron oxide nanoparticles incorporated polymeric ultrafiltration membrane for the removal of toxic pentachlorophenol - Jenet George; Abdullah K. Alanazi; P. Senthil Kumar; Swethaa Venkataraman; Devi Sri Rajendran; Jothyswarupha Krishnakumar Athilakshmi; Isita Singh; Ishani Singh; Pramit sen; Maheswari Purushothaman; Palanisamy Athiyaman Balakumaran; Vinoth Kumar Vaidyanathan; et al. (Chemosphere, 2023)

Techno-economic and environmental sustainability prospects on biochemical conversion of agricultural and algal biomass to biofuels - A. Saravanan; P.R. Yaashikaa; P. Senthil Kumar; A.S. Vickram; S. Karishma; R. Kamalesh; Gayathri Rangasamy (Journal of Cleaner Production, 2023)

Optimizing biogas production from palm oil mill effluent utilizing integrated machine learning and response surface methodology framework - Viggy Wee Gee Tan; Yi Jing Chan; Senthil Kumar Arumugasamy; Jun Wei Lim (Journal of Cleaner Production, 2023)

Palladium nanoparticles anchored MoS2-MXene composite modified electrode for rapid sensing of toxic bisphenol A in aqueous media - A.T. Ezhil Vilian; Jitendra N. Tiwari; Munirah Alhammadi; Gokul Bhaskaran; Seung-Kyu Hwang; Suheon Kim; Krishan Kumar; Annamalai Senthil Kumar; Yun Suk Huh; Young-Kyu Han (Chemical Engineering Journal, 2023)

Type 2 Diabetes (T2DM) and Parkinson’s Disease (PD): a Mechanistic Approach - S. Sri Sabari; Kiruthika Balasubramani; Mahalaxmi Iyer; Harysh Winster Sureshbabu; Dhivya Venkatesan; Abilash Valsala Gopalakrishnan; Arul Narayanaswamy; Nachimuthu Senthil Kumar; Balachandar Vellingiri (Molecular Neurobiology, 2023)

Hepato and renoprotective activity of Kappaphycus alvarezii ethanolic extract in cisplatin causes hepatic and kidney harm in Albino Wistar rats - Annamalai Natarajan; Radhakrishnan Prabakarakrishnan; Kasivelu Govindaraju; Vimal Sugumar; Kuppusamy Sathiskumar; Jayaraman Narenkumar; Aadhikesavan Ramanan; Balasubramanian Senthil Kumar (Aquaculture International, 2023)

Status of disinfection byproducts research in India - Kowsalya Vellingiri; P. Ganesh Kumar; P. Senthil Kumar; S. Jagannathan; S. Kanmani (Chemosphere, 2023)

A biotechnological roadmap for decarbonization systems combined into bioenergy production: Prelude of environmental life-cycle assessment - P.R. Yaashikaa; P. Senthil Kumar; A. Saravanan; S. Karishma; Gayathri Rangasamy (Chemosphere, 2023)

Performance analysis on a compression ignition engine fueled with algae, rice bran methyl esters, and their diesel blends at optimized blend proportion, injection timing and load - Jayaprabakar Jayaraman; T. Arunkumar; P. Senthil Kumar; Anish Mariadhas; Prabhu Appavu; Gayathri Rangasamy (Fuel, 2023)

Drought attenuates plant responses to multiple rhizospheric pathogens: A study on a dry root rot-associated disease complex in chickpea fields - Aswin Reddy Chilakala; Prachi Pandey; Athimoolam Durgadevi; Manu Kandpal; Basavanagouda S. Patil; Krishnappa Rangappa; Puli Chandra Obul Reddy; Venkategowda Ramegowda; Muthappa Senthil‑Kumar (Field Crops Research, 2023)

Removal of pentachlorophenol and phenanthrene from lignocellulosic biorefinery wastewater by a biocatalytic/biosurfactant system comprising cross-linked laccase aggregates and rhamnolipid - Vinoth Kumar Vaidyanathan; P. Senthil Kumar; Isita singh; Ishani singh; Gayathri Rangasamy; Rijuta Ganesh Saratale; Ganesh Dattatraya Saratale (Environmental Pollution, 2023)

Effect of metal ion on optical, photoluminescence, morphological, and photocatalytic properties of ZnS nanoparticles - Selvaraj Vijayan; Ganapathi Umadevi; Ramasamy Mariappan; Chandran Senthil Kumar; Anbalagan Karthikeyan (Environmental Science and Pollution Research, 2023)

Metarhizium indicum, a new species of entomopathogenic fungus infecting leafhopper, Busoniomimus manjunathi from India - C.M. Senthil Kumar; T.K. Jacob; S. Devasahayam; Kunhiraman C. Rajeshkumar; Sneha S. Lad; Sharon D'Silva; C. Geethu (Journal of Invertebrate Pathology, 2023)

Deciphering endemic rhizosphere microbiome community’s structure towards the host-derived heavy metals tolerance and plant growth promotion functions in serpentine geo-ecosystem - Rajendran Senthil Kumar; Suprokash Koner; Hsin-Chi Tsai; Jung-Sheng Chen; Shih- Wei Huang; Bing-Mu Hsu (Journal of Hazardous Materials, 2023)

A review on algae biosorption for the removal of hazardous pollutants from wastewater: Limiting factors, prospects and recommendations - B. Ramesh; A. Saravanan; P. Senthil Kumar; P.R. Yaashikaa; P. Thamarai; Alan Shaji; Gayathri Rangasamy (Environmental Pollution, 2023)

Advances in enzymatic conversion of biomass derived furfural and 5-hydroxymethylfurfural to value-added chemicals and solvents - Vinoth Kumar Vaidyanathan; Kongkona Saikia; P. Senthil Kumar; Abiram Karanam Rathankumar; Gayathri Rangasamy; Ganesh Dattatraya Saratale (Bioresource Technology, 2023)

Cost-effective, scalable production of glucose oxidase using Casuarina equisetifolia biomass and its application in the bio-Fenton oxidation process for the removal of trace organic contaminants from wastewater - Vinoth Kumar Vaidyanathan; Abdullah K. Alanazi; P. Senthil Kumar; Devi Sri Rajendran; Ashok Chidambaram; Swethaa Venkataraman; Vaithyanathan Vasanth Kumar; Gayathri Rangasamy; Hubert Cabana; Hala M. Abo-Dief (Bioresource Technology, 2023)

Correction: Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

Role and mechanistic actions of protein kinase inhibitors as an effective drug target for cancer and COVID - J. Narayanan; T. Tamilanban; P. Senthil Kumar; Ajay Guru; Saravanan Muthupandian; M. K. Kathiravan; Jesu Arockiaraj (Archives of Microbiology, 2023)

Experimental study of the thermal performance of heat storage–integrated solar receiver for parabolic dish collectors - Senthil Kumar Vishnu; Ramalingam Senthil (Environmental Science and Pollution Research, 2023)

Preparation and characterization of a novel cobalt-substitution cadmium aluminate spinel for the photodegradation of azo dye pollutants - G. Rajesh; P. Senthil Kumar; S. Akilandeswari; Gayathri Rangasamy; S. Lohita; V. Uma Shankar; M. Ramya; K. Thirumalai (Chemosphere, 2023)

Fabrication of an effectual, stable and reusable Mg-doped CdAl2O4 nanoparticles for photodegradation of toxic pollutants under visible light illumination - S. Mahalaxmi; G. Rajesh; P. Senthil Kumar; S. Akilandeswari; M. Arul Joshua; V. Uma Shankar; M. Ramya; K. Thirumalai; Gayathri Rangasamy (Chemosphere, 2023)

A sustainable approach on thermal and catalytic conversion of waste plastics into fuels - B. Senthil Rathi; P. Senthil Kumar; Gayathri Rangasamy (Fuel, 2023)

Development of in-situ electrochemical heavy metal ion sensor using integrated 1D/0D/1D hybrid by MWCNT and CQDs supported MnO2 nanomaterial - K. Bhuvaneswari; S. Radha; B.S. Sreeja; P. Senthil Kumar (Environmental Research, 2023)

Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

Efficacy of simultaneous advanced oxidation and adsorption for treating municipal wastewater for indirect potable reuse - P. Ganesh Kumar; S. Kanmani; P. Senthil Kumar; Kowsalya Vellingiri (Chemosphere, 2023)

Strategies for ameliorating the photodegradation efficiency of Mn-doped CdAl2O4 nanoparticles for the toxic dyes under visible light illumination - G. Rajesh; P. Senthil Kumar; S. Akilandeswari; Gayathri Rangasamy; S. Lohita; V. Uma Shankar; M. Ramya; K. Nirmala; K. Thirumalai (Chemosphere, 2023)

Auxin–cytokinin interplay shapes root functionality under low-temperature stress - Manish Tiwari; Ritesh Kumar; Senthil Subramanian; Colleen J. Doherty; S.V. Krishna Jagadish (Trends in Plant Science, 2023)

Process modelling and optimisation of methane yield from palm oil mill effluent using response surface methodology and artificial neural network - Jia Win Chen; Yi Jing Chan; Senthil Kumar Arumugasamy; Sara Kazemi Yazdi (Journal of Water Process Engineering, 2023)

A review on regeneration of biowaste into bio-products and bioenergy: Life cycle assessment and circular economy - A. Saravanan; S. Karishma; P. Senthil Kumar; Gayathri Rangasamy (Fuel, 2023)

A critical review on pyrolysis method as sustainable conversion of waste plastics into fuels - K. Radhakrishnan; P. Senthil Kumar; Gayathri Rangasamy; L. Praveen Perumal; S. Sanaulla; S. Nilavendhan; V. Manivasagan; K. Saranya (Fuel, 2023)

Anti-cancer activity of Hypnea valentiae seaweed loaded gold nanoparticles through EMT signaling pathway in A549 cells - Sandhiya Viswanathan; Thirunavukkarsu Palaniyandi; Dhayan Chand Chellam; Mohammed Fahad Ahmed; Nithin Shoban; M. Pushpakumar; Mugip Rahaman Abdul Wahab; Gomathy Baskar; Maddaly Ravi; Asha Sivaji; Sudhakar Natarajan; Senthil Kumar Sankareswaran (Biochemical Systematics and Ecology, 2023)

Three-phase partitioning for the separation of proteins, enzymes, biopolymers, oils and pigments: a review - Devi Sri Rajendran; Ashok Chidambaram; Ponnusamy Senthil Kumar; Swethaa Venkataraman; Shanmugaprakash Muthusamy; Dai-Viet Nguyen Vo; Gayathri Rangasamy; Vasanth Kumar Vaithyanathan; Vinoth Kumar Vaidyanathan (Environmental Chemistry Letters, 2023)

Utilization of industrial waste - Liquid cheese whey for the batch fermentation of lovastatin using Fusarium nectrioides (MH173849) an endophytic fungus: Screening, production and characterization - Senthamarai Manogaran; Kannan Kilavan Packiam; P. Senthil Kumar; Gayathri Rangasamy; A. Saravanan (Chemosphere, 2023)

A synergistic consequence of catalyst dosage, pH solution and reactive species of Fe-doped CdAl2O4 nanoparticles on the degradation of toxic environmental pollutants - G. Rajesh; P. Senthil Kumar; S. Akilandeswari; Gayathri Rangasamy; Aindrila Mandal; V. Uma Shankar; M. Ramya; K. Nirmala; K. Thirumalai (Chemosphere, 2023)

Microplastics occurrence, detection and removal with emphasis on insect larvae gut microbiota - Louella Concepta Goveas; Sneha Nayak; P. Senthil Kumar; Gayathri Rangasamy; S.M. Vidya; Ramesh Vinayagam; Raja Selvaraj; Dai Viet N. Vo (Marine Pollution Bulletin, 2023)

Erratum to “Temporal expression profiling of GhNAC transcription factor genes in cotton cultivars under abiotic stresses” [Plant Gene 28C (2021) 100334] - S. Sivakumar; G. Prem Kumar; S. Vinoth; G. Siva; M. Vigneswaran; P. Gurusaravanan; M. Kanakachari; T. Senthil Kumar; P. Baskaran; N. Jayabalan (Plant Gene, 2023)

Fish processing discards: A plausible resource for valorization to renewable fuels production, optimization, byproducts and challenges - A. Saravanan; D. Yuvaraj; P. Senthil Kumar; S. Karishma; Gayathri Rangasamy (Fuel, 2023)

RETRACTED: A review on extraction of polysaccharides from crustacean wastes and their environmental applications - A. Saravanan; P. Senthil Kumar; D. Yuvaraj; S. Jeevanantham; P. Aishwaria; P.B. Gnanasri; M. Gopinath; Gayathri Rangasamy (Environmental Research, 2023)

Biodegradation of oil-contaminated aqueous ecosystem using an immobilized fungi biomass and kinetic study - A. Saravanan; S. Karishma; P. Senthil Kumar; Gayathri Rangasamy (Environmental Research, 2023)

Rhizobium mayense sp. Nov., an efficient plant growth-promoting nitrogen-fixing bacteria isolated from rhizosphere soil - Rasheeda Shameem M; Mary Isabella Sonali J; P. Senthil Kumar; Gayathri Rangasamy; K. Veena Gayathri; V. Parthasarathy (Environmental Research, 2023)

The war for apoplastic water: stomatal control as a key strategy in bacterial pathogenesis - Aanchal Choudhary; Muthappa Senthil-Kumar (Journal of Plant Biochemistry and Biotechnology, 2023)

Experimental Investigation on Impact of Diethyl Ether Additives with Cashew Nut Shell Liquid Biodiesel Blends on Performance Characteristics of Engine Operating at Optimum Conditions - D. Senthil kumar; Sivanesan Murugesan (Emission Control Science and Technology, 2023)

Biofortification: A long-term solution to improve global health- a review - G. Monika; S. Rhoda Melanie Kim; P. Senthil Kumar; K. Veena Gayathri; Gayathri Rangasamy; A. Saravanan (Chemosphere, 2023)

Sensing of azo toxic dyes using nanomaterials and its health effects - A review - B. Monisha; Rajalakshmi Sridharan; P. Senthil Kumar; Gayathri Rangasamy; Veena Gayathri Krishnaswamy; S. Subhashree (Chemosphere, 2023)

Efficient decolorization and detoxification of triarylmethane and azo dyes by porous-cross-linked enzyme aggregates of Pleurotus ostreatus laccase - Jenet George; Devi Sri Rajendran; P. Senthil Kumar; Srinidhi Sonai Anand; Vaidyanathan Vinoth Kumar; Gayathri Rangasamy (Chemosphere, 2023)

A review on the applicability of adsorption techniques for remediation of recalcitrant pesticides - Sanchali Bose; P. Senthil Kumar; Gayathri Rangasamy; G. Prasannamedha; S. Kanmani (Chemosphere, 2023)

GO/ZnO nanocomposite - as transducer platform for electrochemical sensing towards environmental applications - P. Senthil Kumar; Padmalaya G; N. Elavarasan; B.S. Sreeja (Chemosphere, 2023)

Strategies for microbial bioremediation of environmental pollutants from industrial wastewater: A sustainable approach - A. Saravanan; Ponnusamy Senthil Kumar; Pham Anh Duc; Gayathri Rangasamy (Chemosphere, 2023)

A critical review on the environmental applications of carbon dots - Akshatha Hebbar; Raja Selvaraj; Ramesh Vinayagam; Thivaharan Varadavenkatesan; Ponnusamy Senthil Kumar; Pham Anh Duc; Gayathri Rangasamy (Chemosphere, 2023)

A review on zeolite catalyst for deNOx performance in ammonia–selective catalytic reduction - M. Sunil Kumar; M.S. Alphin; P. Senthil Kumar; S. Raja (Fuel, 2023)

Isolation of moderately halotolerant bacterial strains, associated with coral Porites lutea from Gulf of Kachchh: Antibacterial activity and PHB production - Rajalakshmi Sridharan; Veena Gayathri Krishnaswamy; P. Senthil Kumar; Manasa Muralidharan; S. Aishwarya; V. Sivamurugan; Chandran Rethnaraj; J.C. Nisha; Chowdula Satyanarayana; Gayathri Rangasamy (Environmental Research, 2023)

Valorization of micro-algae biomass for the development of green biorefinery: Perspectives on techno-economic analysis and the way towards sustainability - A. Saravanan; P. Senthil Kumar; Michael Badawi; Gunda Mohanakrishna; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2023)

Profiling bioactive compounds of Pogostemon benghalensis (Burm.f.) Kuntze and its antibacterial activity - Udayakumar Sandhiya; T. Manikandan; Subbu Thavamurugan; M. R. Kavipriya; Senthil Kumar Pavithra; Azhagiya Manavalan Lakshmi Prabha (Vegetos, 2023)

Sustainable production of biosurfactants via valorisation of industrial wastes as alternate feedstocks - Femina Carolin C; P. Senthil Kumar; Gunda Mohanakrishna; R.V. Hemavathy; Gayathri Rangasamy; Tejraj M Aminabhavi (Chemosphere, 2023)

Mercury sources, contaminations, mercury cycle, detection and treatment techniques: A review - K. Grace Pavithra; P. SundarRajan; P. Senthil Kumar; Gayathri Rangasamy (Chemosphere, 2023)

A study of potent biofertiliser and its degradation ability of monocrotophos and its in silico analysis - Mary Isabella Sonali J; K. Veena Gayathri; P. Senthil Kumar; Gayathri Rangasamy (Chemosphere, 2023)

Adsorptive removal of tetracycline from aqueous solutions using magnetic Fe2O3 / activated carbon prepared from Cynometra ramiflora fruit waste - Raja Selvaraj; Deepa Prabhu; P. Senthil Kumar; Gayathri Rangasamy; Gokulakrishnan Murugesan; Mouli Rajesh; Louella Concepta Goveas; Thivaharan Varadavenkatesan; Adithya Samanth; R. Balakrishnaraja; Ramesh Vinayagam (Chemosphere, 2023)

Strategies for enhancing the efficacy of anaerobic digestion of food industry wastewater: An insight into bioreactor types, challenges, and future scope - A. Saravanan; P. Senthil Kumar; Gayathri Rangasamy; R. Hariharan; R.V. Hemavathy; P.D. Deepika; Krithika Anand; S. Karthika (Chemosphere, 2023)

Assessment of product distribution of plastic waste from catalytic pyrolysis process - Fetcia Jackulin Christopher; P. Senthil Kumar; Lakshmipriya Jayaraman; Gayathri Rangasamy (Fuel, 2023)

Electrodeionization: Principle, techniques and factors influencing its performance - P. Senthil Kumar; M. Varsha; B. Senthil Rathi; Gayathri Rangasamy (Environmental Research, 2023)

Green synthesized cobalt oxide nanoparticles with photocatalytic activity towards dye removal - Ramesh Vinayagam; Akshatha Hebbar; P. Senthil Kumar; Gayathri Rangasamy; Thivaharan Varadavenkatesan; Gokulakrishnan Murugesan; Shikhar Srivastava; Louella Concepta Goveas; N. Manoj Kumar; Raja Selvaraj (Environmental Research, 2023)

Enhancement of antifouling properties, metal ions and protein separation of poly(ether-ether-sulfone) ultrafiltration membranes by incorporation of poly ethylene glycol and n-ZnO - Maheswari Purushothaman; Adhikesavan Harikrishnan; P. Senthil Kumar; Jenet George; Gayathri Rangasamy; Vinoth Kumar Vaidyanathan (Environmental Research, 2023)

Application of Salvinia sps. in remediation of reactive mixed azo dyes and Cr (VI) - Its pathway elucidation - Leena Merlin Biju; Veena Gayathri K; P. Senthil Kumar; R. Kavitha; Revathy Rajagopal; Gayathri Rangasamy (Environmental Research, 2023)

Prevalence of differential microbiome in healthy, diseased and nipped colonies of corals, Porites lutea in the Gulf of Kachchh, north-west coast of India - Veena Gayathri Krishnaswamy; Kabilan Mani; P. Senthil Kumar; Gayathri Rangasamy; Rajalakshmi Sridharan; Chandran Rethnaraj; Sai Sruthi Amirtha Ganesh; Suryasri Kalidas; Vignesh Palanisamy; Nisha Jayasingh Chellama; Satyanarayana Chowdula; V. Parthasarathy; et al. (Environmental Research, 2023)

Systematic assessment of mineral distribution and diversity of microbial communities and its interactions in the Taiwan subduction zone of mud volcanoes - Viji Nagarajan; Hsin-Chi Tsai; Jung-Sheng Chen; Suprokash Koner; Rajendran Senthil Kumar; Hung-Chun Chao; Bing-Mu Hsu (Environmental Research, 2023)

Mixed polyaromatic hydrocarbon degradation by halotolerant bacterial strains from marine environment and its metabolic pathway - Manasa Muralidharan; K. Veena Gayathri; P. Senthil Kumar; D.S. Preethi; R. Kavitha; Revathy Rajagopal; Gayathri Rangasamy (Environmental Research, 2023)

Experimental investigation of the electrochemical detection of sulfamethoxazole using copper oxide-MoS2 modified glassy carbon electrodes - M. Ramya; P. Senthil Kumar; Gayathri Rangasamy; V. Uma Shankar; G. Rajesh; K. Nirmala (Environmental Research, 2023)

Carbon credit reduction: A techno-economic analysis of “drop-in” fuel production - G. Velvizhi; Rishika Nair; Chandamita Goswami; Senthil Kumar Arumugam; Nagaraj P. Shetti; Tejraj M. Aminabhavi (Environmental Pollution, 2023)

Acclimatization of non-cultivated rice landraces to early moisture stress mediated by enzymatic antioxidants and osmolyte accumulation - Asish K. Binodh; Pravin Kumar Kathiresan; Sugitha Thankappan; A. Senthil (Biocatalysis and Agricultural Biotechnology, 2023)

RETRACTED ARTICLE: Carbon dioxide methanation on heterogeneous catalysts: a review - Cham Q. Pham; Mahadi B. Bahari; Ponnusamy Senthil Kumar; Shams Forruque Ahmed; Leilei Xiao; Sunil Kumar; Amjad Saleh Qazaq; Tan Ji Siang; Huu-Tuan Tran; Aminul Islam; Adel Al-Gheethi; Yasser Vasseghian; et al. (Environmental Chemistry Letters, 2022)

Three-dimensional modelling and analysis of early timber scarf joints at Padmanabhapuram palace, Thuckalay, Tamil Nadu - Sherin Alexander; N. Senthil Kumar (Journal of the Indian Academy of Wood Science, 2022)

Pesticide regulation policy and global food safety for Indian spices - Santhosh J. Eapen; Lijo Thomas; R. Praveena; C. M. Senthil Kumar (Journal of Consumer Protection and Food Safety, 2022)

Ameliorative effects of Guilandina bonduc L. aqueous seed extract on letrozole induced polycystic ovary syndrome in female wistar albino rats - Thirumurugan Ayyadurai; Anil Kumar Moola; Prasobh K. Mohan; Senthil Kumar Thiruppathi; Achiraman Shanmugam; Ranjitha Kumari Bollipo Diana (Advances in Traditional Medicine, 2022)

Effect of seaweeds extract and plant growth regulators on high-frequency in vitro regeneration and ex-vitro rooting of Ceropegia maculata Bedd.: an endemic species of Southern Western Ghats - Rengasamy Anbazhakan; Selvaraju Parthibhan; Thiruppathi Senthil Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

A systematic review on the effects of acrylamide and bisphenol A on the development of Drosophila melanogaster - Swetha Senthil Kumar; Abhinaya Swaminathan; Mohamed M. Abdel-Daim; Sahabudeen Sheik Mohideen (Molecular Biology Reports, 2022)

Nature-Inspired Design and Advanced Multi-Computational Investigations on the Mission Profile of a Highly Manoeuvrable Unmanned Amphibious Vehicle for Ravage Removals in Various Oceanic Environments - Vijayanandh Raja; Senthil Kumar Madasamy; Parvathy Rajendran; Sangeetha Ganesan; Dharshini Murugan; Hussein A. Z. AL-bonsrulah; Mohammed Al-Bahrani (Journal of Marine Science and Engineering, 2022)
Recent large-scale operations, including frequent maritime transportation and unauthorised as well as unlawful collisions of drainage wastes, have polluted the ocean’s ecology. Due to the ocean’s unsuitable ecology, the entire globe may experience drastic aberrant conditions, which will force illness onto all living things. Therefore, an advanced system is very necessary to remove the undesired waste from the ocean’s surface and interior. Through the use of progressive unmanned amphibious vehicles (UAV), this study provides a dynamic operational mode-based solution to damage removal. In order to successfully handle the heavy payloads of ravage collections when the UAV reveals centre of gravity concerns, a highly manoeuvrable-based design inspired by nature has been imposed. The ideal creatures to serve as the inspiration for this piece are tropical birds, which have a long tail for navigating tricky situations. The design initialization was carried out by focusing on the outer body of tropical birds. Following this, special calculations were conducted and the full design parameters of the UAV were established. This study proposes a unique mathematical formulation for the development of primary and secondary design parameters of an UAV. The proposed mission profile of this application is computationally tested with the aid of sophisticated computational methodologies after the modelling of this UAV. The computational methods that are required are one-way coupling-based hydro-structural interaction assessments and computational hydrodynamic analyses. Computing is used to determine the aerodynamic and hydrodynamic forces over the UAV, the lightweight materials to withstand high fluid dynamic loads, and the buoyancy forces to complete the UAV components. These computational methods have been used to produce a flexible and fine-tuned UAV design for targeted real-time applications.

Enhanced photodegradation of methylene blue from aqueous solution using Al-doped ZnS nanoparticles - Vijayan Selvaraj; Heba H. Mahboub; Umadevi Ganapathi; Senthil Kumar Chandran; Wedad Al-Onazi; Amal Mohammed Al-Mohaimeed; Tse-Wei Chen; Caterina Faggio; Balaji Paulraj (Environmental Science and Pollution Research, 2022)

Microbial pullulan for food, biomedicine, cosmetic, and water treatment: a review - Subbulakshmi Muthusamy; Swetha Juliet Anandharaj; Ponnusamy Senthil Kumar; Yogesan Meganathan; Dai-Viet Nguyen Vo; Vinoth Kumar Vaidyanathan; Shanmugaprakash Muthusamy (Environmental Chemistry Letters, 2022)

Determination of Multi Elements in Tobacco Plant of Northeast India by Neutron Activation Analysis and Atomic Absorption Spectrometry - Khawlhring Lalrammawia; Ananya Buragohain; Bomngam Kakki; Lalrinawma Zote; Nikrang K. Marak; Lalrinhlupuii; Malsawmtluangi; Rebecca Lalmuanpuii; Nachimuthu Senthil Kumar; Lalrintluanga Jahau; Mathummal Sudarshan; Omari Chaligava; et al. (Biological Trace Element Research, 2022)

Automated weed detection system in smart farming for developing sustainable agriculture - S. V. Jansi Rani; P. Senthil Kumar; R. Priyadharsini; S. Jahnavi Srividya; S. Harshana (International Journal of Environmental Science and Technology, 2022)

Production of hydrogen and value-added carbon materials by catalytic methane decomposition: a review - Cham Q. Pham; Tan Ji Siang; Ponnusamy Senthil Kumar; Zainal Ahmad; Leilei Xiao; Mahadi B. Bahari; Anh Ngoc T. Cao; Natarajan Rajamohan; Amjad Saleh Qazaq; Amit Kumar; Pau Loke Show; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)

Investigation of phytochemicals and antioxidant activity of Plectranthus bourneae Gamble - an endemic plant species of western ghats of Tamil Nadu, India - Raja Thaniarasu; Srinivasan Abirami; Thiruppathi Senthil Kumar; Mandali Venkateswara Rao (Vegetos, 2022)

Study on the use of lightweight expanded perlite and vermiculite aggregates in blended cement mortars - Tzer Sheng Tie; Kim Hung Mo; U. Johnson Alengaram; Senthil Kumar Kaliyavaradhan; Tung-Chai Ling (European Journal of Environmental and Civil Engineering, 2022)

Enhancement of Celastrol compound by silver nanoparticles and acetosyringone in Celastrus paniculatus Willd. through adventitious and hairy root culture - Anil Kumar Moola; T. Senthil Kumar; B. D. Ranjitha Kumari (Journal of Plant Biochemistry and Biotechnology, 2022)

Effect of physiological and morphological response of Musa acuminata under stress condition with different salinity levels using IoT - P. Manojkumar; A. Dheepanchakkravarthy; P. Senthil Kumar; S. Tamilsevi; C. Srinivasan (International Journal of Environmental Science and Technology, 2022)

Biocatalytic polymeric membranes to decrease biofilm fouling and remove organic contaminants in wastewater: a review - Jenet George; Srinidhi Sonai Anand; Ponnusamy Senthil Kumar; Priyanka Saravanan; Rashmi Lenin; Devi Sri Rajendran; Swethaa Venkataraman; Vinoth Kumar Vaidyanathan; Dai-Viet Nguyen Vo (Environmental Chemistry Letters, 2022)

Advanced catalysts and effect of operating parameters in ethanol dry reforming for hydrogen generation. A review - Mohd-Nasir Nor Shafiqah; Tan Ji Siang; Ponnusamy Senthil Kumar; Zainal Ahmad; A. A. Jalil; Mahadi B. Bahari; Quyet Van Le; Leilei Xiao; M. Mofijur; Changlei Xia; Shams Forruque Ahmed; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)

Degradation and detoxification of reactive yellow dyes by Scedosporium apiospermum: a mycoremedial approach - Varuna Kumaravel; Paul Olusegun Bankole; Baby Jooju; Senthil Kumar Sadasivam (Archives of Microbiology, 2022)

Effects of air pollution on monumental buildings in India: An overview - Narayanan Natarajan; Mangottiri Vasudevan; Senthil Kumar Dineshkumar; Sivakkumar Shiva Nandhini; Pandiyan Balaganesh (Environmental Science and Pollution Research, 2022)

Chemical, physical and biological methods to convert lignocellulosic waste into value-added products. A review - Selvakumar Periyasamy; V. Karthik; P. Senthil Kumar; J. Beula Isabel; Tatek Temesgen; B. M. Hunegnaw; B. B. Melese; Badr A. Mohamed; Dai-Viet Nguyen Vo (Environmental Chemistry Letters, 2022)

Green synthesis of ZrO2 nanoparticles and nanocomposites for biomedical and environmental applications: a review - Thuan Van Tran; Duyen Thi Cam Nguyen; Ponnusamy Senthil Kumar; Azam Taufik Mohd Din; Aishah Abdul Jalil; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)

Invasive plants as biosorbents for environmental remediation: a review - Duyen Thi Cam Nguyen; Thuan Van Tran; Ponnusamy Senthil Kumar; Azam Taufik Mohd Din; Aishah Abdul Jalil; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)

In vitro micropropagation, flowering, and tuberization of Ceropegia maculata Bedd.—an endemic plant of Southern Western Ghats - Rengasamy Anbazhakan; Chinnaiyan Rajasekar; Mariappan Muthukumar; Selvaraju Parthibhan; Thiruppathi Senthil Kumar (In Vitro Cellular & Developmental Biology - Plant, 2022)

Dynamic simulation of airborne pollutant concentrations associated with the effect of climate change in Batu Muda region, Malaysia - Cedric Lemuel Lee; Wong Yong Jie; Senthil Kumar Arumugasamy (Modeling Earth Systems and Environment, 2022)

Green synthesis of copper nanoparticles using Sesbania aculeata to enhance the plant growth and antimicrobial activities - V. Tamil Elakkiya; R. V. Meenakshi; P. Senthil Kumar; V. Karthik; K. Ravi Shankar; P. Sureshkumar; A. Hanan (International Journal of Environmental Science and Technology, 2022)

Upcycling of wastes for sustainable controlled low-strength material: A review on strength and excavatability - Senthil Kumar Kaliyavaradhan; Tung-Chai Ling; Ming-Zhi Guo (Environmental Science and Pollution Research, 2022)

Malaria Elimination in Two Endemic Coastal Environments of Southern India: An Eco-Epidemiological Analysis from 2004 to 2019 - Appadurai Daniel Reegan; Chandrabose Senthil Kumar; Johnson Amala Justin; Pandia Nadar Udhayakumar; Shanmugasundaram Balavinayagam; Palaniyandi Tamilmaran; Angaiah Natesan; Sundararaj Gopinath; Nirmal Joe; Roshini Arthur (Acta Parasitologica, 2022)

Potential of Biochar as Soil Amendment: Prediction of Elemental Ratios from Pyrolysis of Agriculture Biomass Using Artificial Neural Network - Yi Wei Liew; Senthil Kumar Arumugasamy; Anurita Selvarajoo (Water, Air, & Soil Pollution, 2022)

Stability of biochar derived from banana peel through pyrolysis as alternative source of nutrient in soil: feedforward neural network modelling study - Hong Kai Bong; Anurita Selvarajoo; Senthil Kumar Arumugasamy (Environmental Monitoring and Assessment, 2022)

Extraction, purification and applications of biosurfactants based on microbial-derived glycolipids and lipopeptides: a review - Swethaa Venkataraman; Devi Sri Rajendran; Ponnusamy Senthil Kumar; Dai-Viet Nguyen Vo; Vinoth Kumar Vaidyanathan (Environmental Chemistry Letters, 2022)

Lab-on-a-chip technologies for food safety, processing, and packaging applications: a review - Adithya Sridhar; Ashish Kapoor; Ponnusamy Senthil Kumar; Muthamilselvi Ponnuchamy; Balasubramanian Sivasamy; Dai-Viet Nguyen Vo (Environmental Chemistry Letters, 2022)

Green technology for sustainable surface protection of steel from corrosion: a review - Fatema Said Zahir Said Al Shibli; Subrajit Bose; P. Senthil Kumar; M. Rajasimman; N. Rajamohan; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)

Methods for chemical conversion of plastic wastes into fuels and chemicals. A review - Fetcia Jackulin Christopher; Ponnusamy Senthil Kumar; Dai-Viet Nguyen Vo; Femina Carolin Christopher; Lakshmipriya Jayaraman (Environmental Chemistry Letters, 2022)

Two-dimensional hybrid perovskite solar cells: a review - T. Marimuthu; R. Yuvakkumar; P. Senthil Kumar; Dai-Viet N. Vo; Xueqing Xu; Gang Xu (Environmental Chemistry Letters, 2022)

Biodegradation of Reactive Red 198 by textile effluent adapted microbial strains - Sheela Thangaraj; Paul Olusegun Bankole; Senthil Kumar Sadasivam; Varuna Kumarvel (Archives of Microbiology, 2022)

Complex molecular mechanisms determine fitness of plants to biotic and abiotic stresses - Ashish Prasad; Muthappa Senthil-Kumar; Manoj Prasad (Journal of Plant Biochemistry and Biotechnology, 2021)

Editorial - Manoj Prasad; Muthappa Senthil-Kumar (Journal of Plant Biochemistry and Biotechnology, 2021)

Investigation of the novel transcriptional changes under combined drought and bacterial stress underpins the role of AtMYB96 in imparting tolerance - Aanchal Choudhary; Muthappa Senthil-Kumar (Journal of Plant Biochemistry and Biotechnology, 2021)

The ins and outs of SWEETs in plants: Current understanding of the basics and their prospects in crop improvement - Anjali Anjali; Urooj Fatima; Muthappa Senthil-Kumar (Journal of Biosciences, 2021)

Conversion of waste plastics into low emissive hydrocarbon fuel using catalyst produced from biowaste - Nandakumar Jahnavi; Kumar Kanmani; Ponnusamy Senthil Kumar; Sunita Varjani (Environmental Science and Pollution Research, 2021)

Biogas upgrading, economy and utilization: a review - Shams Forruque Ahmed; M. Mofijur; Karishma Tarannum; Anika Tasnim Chowdhury; Nazifa Rafa; Samiha Nuzhat; P. Senthil Kumar; Dai-Viet N. Vo; Eric Lichtfouse; T. M. I. Mahlia (Environmental Chemistry Letters, 2021)

Modelling of adsorption of anionic azo dye using Strychnos potatorum Linn seeds (SPS) from aqueous solution with artificial neural network (ANN) - Wei Wen Wee; Mei Yuen Siau; Senthil Kumar Arumugasamy; Kirupa Sankar Muthuvelu (Environmental Monitoring and Assessment, 2021)

Graphene-based materials for environmental applications: a review - V. Karthik; P. Selvakumar; P. Senthil Kumar; Dai-Viet N. Vo; M. Gokulakrishnan; P. Keerthana; V. Tamil Elakkiya; R. Rajeswari (Environmental Chemistry Letters, 2021)

Microwave pyrolysis of coal, biomass and plastic waste: a review - Aravind Suresh; Alaguabirami Alagusundaram; Ponnusamy Senthil Kumar; Dai-Viet Nguyen Vo; Femina Carolin Christopher; Bharkavi Balaji; Vinatha Viswanathan; Sibi Sankar (Environmental Chemistry Letters, 2021)

Biochar promotes methane production during anaerobic digestion of organic waste - Leilei Xiao; Eric Lichtfouse; P. Senthil Kumar; Quan Wang; Fanghua Liu (Environmental Chemistry Letters, 2021)

Mapping and Electronic Publishing of Shoreline Changes using UAV Remote Sensing and GIS - N. Shenbagaraj; K. Senthil kumar; A. Mohamed Rasheed; J. Leostalin; M. Naresh Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Effect of nanoparticle-blended biodiesel mixtures on diesel engine performance, emission, and combustion characteristics - Senthil Kumar Srinivasan; Rajan Kuppusamy; Purushothaman Krishnan (Environmental Science and Pollution Research, 2021)

Microbial degradation of recalcitrant pesticides: a review - Sanchali Bose; P. Senthil Kumar; Dai-Viet N. Vo; N. Rajamohan; R. Saravanan (Environmental Chemistry Letters, 2021)

Advanced techniques to remove phosphates and nitrates from waters: a review - Karthik Velusamy; Selvakumar Periyasamy; Ponnusamy Senthil Kumar; Dai-Viet Nguyen Vo; Jaisankar Sindhu; Dhanabal Sneka; Balakrishnan Subhashini (Environmental Chemistry Letters, 2021)

Techniques and modeling of polyphenol extraction from food: a review - Adithya Sridhar; Muthamilselvi Ponnuchamy; Ponnusamy Senthil Kumar; Ashish Kapoor; Dai-Viet N. Vo; Sivaraman Prabhakar (Environmental Chemistry Letters, 2021)

Investigation of EG-Bi2S3 nanorods photocatalytic activity under visible light for dye degradation from aquatic system - Subramanian Keerthana; Rathinam Yuvakkumar; Ponnnusamy Senthil Kumar; Ganesan Ravi; Dhayalan Velauthapillai; Dai-Viet Nguyen Vo (Environmental Science and Pollution Research, 2021)

Plant viral vectors: expanding the possibilities of precise gene editing in plant genomes - Stuti Kujur; Muthappa Senthil-Kumar; Rahul Kumar (Plant Cell Reports, 2021)

Sustainable adsorbents for the removal of pesticides from water: a review - Muthamilselvi Ponnuchamy; Ashish Kapoor; Ponnusamy Senthil Kumar; Dai-Viet N. Vo; Akash Balakrishnan; Meenu Mariam Jacob; Prabhakar Sivaraman (Environmental Chemistry Letters, 2021)

Enzyme-loaded nanoparticles for the degradation of wastewater contaminants: a review - V. Karthik; P. Senthil Kumar; Dai-Viet N. Vo; P. Selvakumar; M. Gokulakrishnan; P. Keerthana; V. Audilakshmi; J. Jeyanthi (Environmental Chemistry Letters, 2021)

Sorghum mitigates climate variability and change on crop yield and quality - Keerthi Chadalavada; B. D. Ranjitha Kumari; T. Senthil Kumar (Planta, 2021)

Occurrence and removal of antibiotics from industrial wastewater - D. Akhil; Divya Lakshmi; P. Senthil Kumar; Dai-Viet N. Vo; A. Kartik (Environmental Chemistry Letters, 2021)

Hydrothermal production of algal biochar for environmental and fertilizer applications: a review - V. Karthik; P. Senthil Kumar; Dai-Viet N. Vo; J. Sindhu; D. Sneka; B. Subhashini; K. Saravanan; J. Jeyanthi (Environmental Chemistry Letters, 2021)

Food preservation techniques and nanotechnology for increased shelf life of fruits, vegetables, beverages and spices: a review - Adithya Sridhar; Muthamilselvi Ponnuchamy; Ponnusamy Senthil Kumar; Ashish Kapoor (Environmental Chemistry Letters, 2021)

Sequential production of hydrogen and methane by anaerobic digestion of organic wastes: a review - Salma Aathika Abdur Rawoof; P. Senthil Kumar; Dai-Viet N. Vo; Sivanesan Subramanian (Environmental Chemistry Letters, 2021)

Lidar-aided Autonomous Landing and Vision-based Taxiing for Fixed-Wing UAV - K. Senthil Kumar; M. Venkatesan; S. Karuppaswamy (Journal of the Indian Society of Remote Sensing, 2021)

Modeling Seasonal Variation in Urban Weather in Sub-Tropical Region of Delhi - Kshama Gupta; Pushplata; Allaka Lalitha; Payel Ghosh Dastidar; Jillela Malleswara Rao; Praveen Thakur; Jai Shankar Gummapu; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Application of UAV Remote Sensing Technology for Sand Quarry Volumetric Audit and Environmental Impact Assessment: A Case Study Done in Neyvasal Sand Quarry, Cuddalore District, Tamil Nadu—India - J. Leo Stalin; K. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Macro-, micro-, and trace element distributions in areca nut, husk, and soil of northeast India - Lalrinawma Zote; Khawlhring Lalrammawia; Ananya Buragohain; Lalrinhlupuii; Bomngam Kakki; Rebecca Lalmuanpuii; Zodinpuia Pachuau; John Vanlalhruaia; Rajendra Bose Muthukumaran; Nachimuthu Senthil Kumar; Lalrintluanga Jahau; Mathummal Sudarshan; et al. (Environmental Monitoring and Assessment, 2021)

Fish gill microbiome from India’s largest Brahmaputra River—a trans-border biodiversity hotspot region - Dipika Malakar; Subbarayan Sarathbabu; Probodh Borah; Nachimuthu Senthil Kumar (Environmental Monitoring and Assessment, 2021)

Techniques of lipid extraction from microalgae for biofuel production: a review - Sze Ying Lee; Ianatul Khoiroh; Dai-Viet N. Vo; P. Senthil Kumar; Pau Loke Show (Environmental Chemistry Letters, 2021)

Production of optically pure lactic acid by microbial fermentation: a review - Salma Aathika Abdur Rawoof; P. Senthil Kumar; Dai-Viet N. Vo; Kubendran Devaraj; Yuvarani Mani; Thiruselvi Devaraj; Sivanesan Subramanian (Environmental Chemistry Letters, 2021)

Photocatalysis for removal of environmental pollutants and fuel production: a review - Anbalagan Saravanan; Ponnusamy Senthil Kumar; Dai-Viet N. Vo; Ponnambalam Ragini Yaashikaa; Suresh Karishma; Sathasivam Jeevanantham; B. Gayathri; V. Dhivya Bharathi (Environmental Chemistry Letters, 2021)

Methods of detection of food-borne pathogens: a review - A. Saravanan; P. Senthil Kumar; R. V. Hemavathy; S. Jeevanantham; R. Kamalesh; S. Sneha; P. R. Yaashikaa (Environmental Chemistry Letters, 2021)

Analysis and removal of pharmaceutical residues from wastewater using membrane bioreactors: a review - C. Femina Carolin; P. Senthil Kumar; G. Janet Joshiba; V. Vinoth Kumar (Environmental Chemistry Letters, 2021)

Co-fired anode-supported solid oxide fuel cell for internal reforming of hydrocarbon fuel - S. Senthil Kumar; Vikram Jayaram; S. T. Aruna (Energy, Ecology and Environment, 2021)

From Guest Editors’ Desk - Shailesh R. Nayak; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Remembering IRS-1C Mission: The “Game Changer” of Indian Earth Observation Program - A. Senthil Kumar; N. Aparna; Shailesh R. Nayak (Journal of the Indian Society of Remote Sensing, 2021)

Magnetite encapsulated alginates tailored material for the sustainable treatment of electroplating industrial wastewater: column dynamics and mass transfer studies - K. Nithya; Asha Sathish; P. Senthil Kumar (Clean Technologies and Environmental Policy, 2021)

Sustainable approach to decolourize methyl orange dye from aqueous solution using novel bacterial strain and its metabolites characterization - C. Femina Carolin; P. Senthil Kumar; G. Janet Joshiba (Clean Technologies and Environmental Policy, 2021)

DNA barcoding and genetic fidelity assessment of micropropagated Aenhenrya rotundifolia (Blatt.) C.S. Kumar and F.N. Rasm.: a critically endangered jewel orchid - N. Ahamed Sherif; T. Senthil Kumar; M. V. Rao (Physiology and Molecular Biology of Plants, 2020)

A review on three-dimensional eletrochemical systems: analysis of influencing parameters and cleaner approach mechanism for wastewater - Kirubanandam GracePavithra; P. Senthil Kumar; V. Jaikumar; PanneerSelvam SundarRajan (Reviews in Environmental Science and Bio/Technology, 2020)

Microalgae for biofuel production and removal of heavy metals: a review - Kirubanandam Grace Pavithra; P. Senthil Kumar; V. Jaikumar; Kilaru Harsha Vardhan; PanneerSelvam SundarRajan (Environmental Chemistry Letters, 2020)

Fibroin gene expression and antioxidant enzymes are elevated in Bombyx mori when reared on preferred host plants - Ruth Lalfelpuii; Souvik Ghatak; Sarathbabu Subbarayan; Bidyut Nath Choudhury; Guruswami Gurusubramanian; Nachimuthu Senthil Kumar (Biologia, 2020)

Modeling and Cr(VI) ion uptake kinetics of Sorghum bicolor plant assisted by plant growth–promoting Pannonibacter phragmetitus: an ecofriendly approach - Ponnambalam Ragini Yaashikaa; Ponnusamy Senthil Kumar; Anbalagan Saravanan (Environmental Science and Pollution Research, 2020)

Fabrication of novel amine-functionalized magnetic silica nanoparticles for toxic metals: kinetic and isotherm modeling - Ganesan Janet Joshiba; Ponnusamy Senthil Kumar; Femina Carolin Christopher; Gowri Pooja; Vaidyanathan Vinoth Kumar (Environmental Science and Pollution Research, 2020)

Comparative study of artificial neural network (ANN), adaptive neuro-fuzzy inference system (ANFIS) and multiple linear regression (MLR) for modeling of Cu (II) adsorption from aqueous solution using biochar derived from rambutan (Nephelium lappaceum) peel - Yong Jie Wong; Senthil Kumar Arumugasamy; Chang Han Chung; Anurita Selvarajoo; Vasanthi Sethu (Environmental Monitoring and Assessment, 2020)

Electrodeionization theory, mechanism and environmental applications. A review - B. Senthil Rathi; P. Senthil Kumar (Environmental Chemistry Letters, 2020)

Artificial Neural Network (ANN) Modelling of Palm Oil Mill Effluent (POME) Treatment with Natural Bio-coagulants - Nurul Asyikin Mohd Najib; Vasanthi Sethu; Senthil Kumar Arumugasamy; Anurita Selvarajoo (Environmental Processes, 2020)

Enhancement of biofuel production by microalgae using cement flue gas as substrate - Senthil Nagappan; Pei-Chien Tsai; Saravanan Devendran; Vardhini Alagarsamy; Vinoth Kumar Ponnusamy (Environmental Science and Pollution Research, 2020)

Conversion of green algal biomass into bioenergy by pyrolysis. A review - S. Aravind; P. Senthil Kumar; Nikhil S. Kumar; N. Siddarth (Environmental Chemistry Letters, 2020)

Implications of intense biomass burning over Uttarakhand in April–May 2016 - Shuchita Srivastava; A. Senthil Kumar (Natural Hazards, 2020)

An experimental and modelling approach to produce biochar from banana peels through pyrolysis as potential renewable energy resources - Anurita Selvarajoo; Dinie Muhammad; Senthil Kumar Arumugasamy (Modeling Earth Systems and Environment, 2020)

Association of tobacco smoke–infused water (tuibur) use by Mizo people and risk of Helicobacter pylori infection - Subhajit Mukherjee; Sreenath Arekurnnath Madathil; Souvik Ghatak; Lalrintluanga Jahau; Jeremy L. Pautu; John Zohmingthanga; Lalawmpuii Pachuau; Belinda Nicolau; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2020)

Antiquorum sensing and antibiofilm potential of biosynthesized silver nanoparticles of Myristica fragrans seed extract against MDR Salmonella enterica serovar Typhi isolates from asymptomatic typhoid carriers and typhoid patients - Senthilkumar Balakrishnan; Kalibulla Syed Ibrahim; Senbagam Duraisamy; Ilakkia Sivaji; Selvam Kandasamy; Anbarasu Kumarasamy; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2020)

Clinical features and first degree relative breast cancer, their correlation with histological tumor grade: a 5-year retrospective case study of breast cancer in Mizoram, India - Doris Zodinpuii; Jeremy Lalrinsanga Pautu; Bawitlung Zothankima; Lalawmpuii Pachuau; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2020)

Plant–microbe interaction: prospects for crop improvement and management - Karaba N. Nataraja; T. S. Suryanarayanan; R. Uma Shaanker; Muthappa Senthil-Kumar; Ralf Oelmüller (Plant Physiology Reports, 2019)

Plant-pathogen interaction in the presence of abiotic stress: What do we know about plant responses? - Prachi Pandey; Muthappa Senthil-Kumar (Plant Physiology Reports, 2019)

Arabidopsis exhibits differential response in basal immunity and proline metabolism during defense against host and nonhost pathogen infection - Aarzoo Qamar; Muthappa Senthil-Kumar (Plant Physiology Reports, 2019)

Cathepsin D Degradable Dendrimer-MPEG-Histone 3-Enrofloxacin Conjugate Nanovehicle for Target Specific Bovine Mastitis Therapy - P. Senthil Kumar; Sambandam Anandan; N. Subramanian (International Journal of Peptide Research and Therapeutics, 2019)

Assessment of historical forest cover loss and fragmentation in Asian elephant ranges in India - Hitendra Padalia; Surajit Ghosh; C. Sudhakar Reddy; Subrata Nandy; Sarnam Singh; A. Senthil Kumar (Environmental Monitoring and Assessment, 2019)

Evaluating sensitivity of hyperspectral indices for estimating mangrove chlorophyll in Middle Andaman Island, India - Rajee George; Hitendra Padalia; S. K. Sinha; A. Senthil Kumar (Environmental Monitoring and Assessment, 2019)

Amplicon sequencing and imputed metagenomic analysis of waste soil and sediment microbiome reveals unique bacterial communities and their functional attributes - Surajit De Mandal; Vabeiryureilai Mathipi; Rajendra Bose Muthukumaran; Guruswami Gurusubramanian; Esther Lalnunmawii; Nachimuthu Senthil Kumar (Environmental Monitoring and Assessment, 2019)

Treatment of fluoride-contaminated water. A review - P. Senthil Kumar; S. Suganya; S. Srinivas; S. Priyadharshini; M. Karthika; R. Karishma Sri; V. Swetha; Mu. Naushad; Eric Lichtfouse (Environmental Chemistry Letters, 2019)

Optimized in vitro micro-tuber production for colchicine biosynthesis in Gloriosa superba L. and its anti-microbial activity against Candida albicans - Sivakumar Subiramani; Sathish Sundararajan; Siva Govindarajan; Vinoth Sadasivam; Prem Kumar Ganesan; Gurusaravanan Packiaraj; Vigneswaran Manickam; Senthil Kumar Thiruppathi; Sathishkumar Ramalingam; Jayabalan Narayanasamy (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Pan coefficients for estimating open-water surface evaporation for a humid tropical monsoon climate region in India - Suhas D Khobragade; Prabhat Semwal; A R Senthil Kumar; H C Nainwal (Journal of Earth System Science, 2019)

Performance and emission reduction characteristics of cerium oxide nanoparticle-water emulsion biofuel in diesel engine with modified coated piston - Elumalai Perumal Venkatesan; Annamalai Kandhasamy; Arularasu Sivalingam; Appuraja Senthil Kumar; KrishnaMoorthy Ramalingam; Paul james thadhani Joshua; Dhinesh Balasubramanian (Environmental Science and Pollution Research, 2019)

Fungal-mediated synthesis of pharmaceutically active silver nanoparticles and anticancer property against A549 cells through apoptosis - Tahira Akther; Vabeiryureilai Mathipi; Nachimuthu Senthil Kumar; MubarakAli Davoodbasha; Hemalatha Srinivasan (Environmental Science and Pollution Research, 2019)

Correction to: Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut - Geetha Govind; Harshavardhan Vokkaliga ThammeGowda; Patricia Jayaker Kalaiarasi; Dhanalakshmi Ramchandra Iyer; Senthil Kumar Muthappa; Sreenivasulu Nese; Udaya Kumar Makarla (Molecular Genetics and Genomics, 2019)

Modelling on the Removal of Dye from Industrial Wastewater Using Surface Improved Enteromorpha intestinalis - Anbalagan Saravanan; Ponnusamy Senthil Kumar; Ponnambalam Ragini Yaashikaa; Selvaraj Kanmani; Ravi Hamsha Varthine; Chinakannu Marimuthu Mathan Muthu; Dinakarkumar Yuvaraj (International Journal of Environmental Research, 2019)

Isolation, characterization, and therapeutic activity of bergenin from marlberry (Ardisia colorata Roxb.) leaf on diabetic testicular complications in Wistar albino rats - Sanasam Sanjeev; Meesala Krishna Murthy; Maibam Sunita Devi; Maurya Khushboo; Zothanmawii Renthlei; Kalibulla Syed Ibrahim; Nachimuthu Senthil Kumar; Vikas Kumar Roy; Guruswami Gurusubramanian (Environmental Science and Pollution Research, 2019)

Monocrotophos, Its Toxic Effect (dermal) on Eisenia fetida (Savigny) - Senthil Kumar Abbiramy; Veeramani Vinitha; Gunasekaran Sangeetha; Mohandoss Monisha (Toxicology and Environmental Health Sciences, 2018)

Reservoir Sedimentation Assessment Through Remote Sensing and Hydrological Modelling - Rahimov Foteh; Vaibhav Garg; Bhaskar Ramchandra Nikam; Madhusudan Y. Khadatare; Shiv Prasad Aggarwal; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2018)

Lifestyle chemical carcinogens associated with mutations in cell cycle regulatory genes increases the susceptibility to gastric cancer risk - Ravi Prakash Yadav; Souvik Ghatak; Payel Chakraborty; Freda Lalrohlui; Ravi Kannan; Rajeev Kumar; Jeremy L. Pautu; John Zomingthanga; Saia Chenkual; Rajendra Muthukumaran; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2018)

Performance comparison of feedforward neural network training algorithms in modeling for synthesis of polycaprolactone via biopolymerization - Y. J. Wong; Senthil Kumar Arumugasamy; J. Jewaratnam (Clean Technologies and Environmental Policy, 2018)

Species Mapping Using Citizen Science Approach Through IBIN Portal: Use Case in Foothills of Himalaya - Priyanka Singh; Sameer Saran; Dheeraj Kumar; Hitendra Padalia; Ashutosh Srivastava; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2018)

George Joseph and C. Jeganathan: Fundamentals of Remote Sensing - Vinay K. Dadhwal; Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2018)

Combining the FCM Classifier with Various Kernels to Handle Non-linearity of Class Boundaries - Akshara Preethy Byju; Anil Kumar; Alfred Stein; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2018)

A Case of Pseudo-RBD with OSA - Abhishek Goyal; Kamendra Singh Pawar; Alkesh Khurana; Senthil Kumar (Sleep and Vigilance, 2018)

Utilities of Virtual 3D City Models Based on CityGML: Various Use Cases - Sameer Saran; Kapil Oberai; Parag Wate; Amol Konde; Arnab Dutta; Kavisha Kumar; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2018)

Forest Fire Burnt Area Assessment in the Biodiversity Rich Regions Using Geospatial Technology: Uttarakhand Forest Fire Event 2016 - Stutee Gupta; Arijit Roy; Dhruval Bhavsar; Rajkanti Kala; Sarnam Singh; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2018)

A Spectro-radiometric Analysis of Ocean Colour Sensors and Proposal for a Miniature Hyper Spectral Imager for Future - R. M. Samudraiah Desu; Ashutosh Kumar Jha; Senthil Kumar Arumugam; V. N. Krishna Murthy Yelisetty; Ujjwal Kumar; Kusum Arunachalam (Journal of the Indian Society of Remote Sensing, 2018)

Somatic embryogenesis, acclimatization and genetic homogeneity assessment of regenerated plantlets of Anoectochilus elatus Lindl., an endangered terrestrial jewel orchid - N. Ahamed Sherif; J. H. Franklin Benjamin; T. Senthil Kumar; M. V. Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Testicular toxicity and sperm quality following copper exposure in Wistar albino rats: ameliorative potentials of L-carnitine - Maurya Khushboo; Meesala Krishna Murthy; Maibam Sunita Devi; Sanasam Sanjeev; Kalibulla Syed Ibrahim; Nachimuthu Senthil Kumar; Vikas Kumar Roy; Guruswami Gurusubramanian (Environmental Science and Pollution Research, 2018)

Fabrication and characterization of a nanocomposite hydrogel for combined photocatalytic degradation of a mixture of malachite green and fast green dye - Gaurav Sharma; Zeid Abdullah ALOthman; Amit Kumar; Shweta Sharma; Senthil Kumar Ponnusamy; Mu. Naushad (Nanotechnology for Environmental Engineering, 2017)

Development of CityGML Application Domain Extension for Indoor Routing and Positioning - Arnab Dutta; Sameer Saran; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2017)

Wheat Monitoring by Using Kernel Based Possibilistic c-Means Classifier: Bi-sensor Temporal Multi-spectral Data - Rohit Nandan Tripathi; Ranjeet Kumar; Anil Kumar; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2017)

In vitro and in vivo anti-proliferative evaluation of bis(4′-(4-tolyl)-2,2′:6′,2″-terpyridine)copper(II) complex against Ehrlich ascites carcinoma tumors - Dharmasivam Mahendiran; Raju Senthil Kumar; Vijayan Viswanathan; Devadasan Velmurugan; Aziz Kalilur Rahiman (JBIC Journal of Biological Inorganic Chemistry, 2017)

Genome-wide characterization and stress-responsive expression profiling of MCM genes in Brassica oleracea and Brassica rapa - Ashokraj Shanmugam; Arif Hasan Khan Robin; Senthil Kumar Thamilarasan; Harshavardhanan Vijayakumar; Sathishkumar Natarajan; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Journal of Plant Biology, 2017)

Evaluation of remote-sensing-based models of gross primary productivity over Indian sal forest using flux tower and MODIS satellite data - T. Watham; N. R. Patel; S. P. S. Kushwaha; V. K. Dadhwal; A. Senthil Kumar (International Journal of Remote Sensing, 2017)

Adsorption of Copper(II) Ion from Aqueous Solution Using Biochar Derived from Rambutan (Nepheliumlappaceum) Peel: Feedforward Neural Network Modelling Study - Manimala Selvanathan; Khoo Tiong Yann; Chang Han Chung; Anurita Selvarajoo; Senthil Kumar Arumugasamy; Vasanthi Sethu (Water, Air, & Soil Pollution, 2017)

Geographical distribution of traits and diversity in the world collection of pearl millet [Pennisetum glaucum (L.) R. Br., synonym: Cenchrus americanus (L.) Morrone] landraces conserved at the ICRISAT genebank - H. D. Upadhyaya; K. N. Reddy; M. Irshad Ahmed; Vinod Kumar; M. K. Gumma; Senthil Ramachandran (Genetic Resources and Crop Evolution, 2017)

Assessment of large aperture scintillometry for large-area surface energy fluxes over an irrigated cropland in north India - Abhishek Danodia; V K Sehgal; N R Patel; R Dhakar; J Mukherjee; S K Saha; A Senthil Kumar (Journal of Earth System Science, 2017)

Estimation of Snow Cover Area, Snow Physical Properties and Glacier Classification in Parts of Western Himalayas Using C-Band SAR Data - Praveen K. Thakur; S. P. Aggarwal; G. Arun; Sahil Sood; A. Senthil Kumar; Sneh Mani; D. P. Dobhal (Journal of the Indian Society of Remote Sensing, 2017)

Biosynthesis of silver nanoparticles using Myristica fragrans seed (nutmeg) extract and its antibacterial activity against multidrug-resistant (MDR) Salmonella enterica serovar Typhi isolates - Senthilkumar Balakrishnan; Ilakkia Sivaji; Selvam Kandasamy; Senbagam Duraisamy; Nachimuthu Senthil Kumar; Guruswami Gurusubramanian (Environmental Science and Pollution Research, 2017)

Land Cover Classification Using ICESat/GLAS Full Waveform Data - S. Ghosh; S. Nandy; S. Patra; S. P. S. Kushwaha; A. Senthil Kumar; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2017)

Micropropagation, in vitro flowering, and tuberization in Brachystelma glabrum Hook.f., an endemic species - S. Revathi Lakshmi; S. Parthibhan; N. Ahamed Sherif; T. Senthil Kumar; M.V. Rao (In Vitro Cellular & Developmental Biology - Plant, 2017)

Dengue scenario: Chennai perspective—a six-year study (2009-2014) - P. Padmapriya; V. Senthil Kumar; R. Senthil Raja; A. Khaleefathullah Sheriff; T. S. Uma; S. Mohana; Kavita Arunagiri; A. Anupama; N. Saran; R. Kiruba; K. Saravana Murali; B. V. Suresh Babu; et al. (Archives of Virology, 2017)

Review of the Book “India’s Journey Towards Excellence in Building Earth Observation Cameras” by Dr. George Joseph, Notion Press, India, 2016 - A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2016)

Synthesis, antimicrobial and cytotoxic evaluation of spirooxindole[pyrano-bis-2H-l-benzopyrans] - K. Parthasarathy; Chandrasekar Praveen; K. Saranraj; C. Balachandran; P. Senthil Kumar (Medicinal Chemistry Research, 2016)

Silver nitrate promotes high-frequency multiple shoot regeneration in cotton (Gossypium hirsutum L.) by inhibiting ethylene production and phenolic secretion - G. Prem Kumar; S. Sivakumar; G. Siva; M. Vigneswaran; T. Senthil Kumar; N. Jayabalan (In Vitro Cellular & Developmental Biology - Plant, 2016)

Influence of shifting cultivation practices on soil–plant–beetle interactions - Kalibulla Syed Ibrahim; Marcy D. Momin; R. Lalrotluanga; David Rosangliana; Souvik Ghatak; R. Zothansanga; Nachimuthu Senthil Kumar; Guruswami Gurusubramanian (Environmental Science and Pollution Research, 2016)

A rapid and reliable method for estimating microalgal biomass using a moisture analyser - Sachitra Kumar Ratha; Polur Hanumantha Rao; Kanchan Govindaswamy; Rajeshkumar Sam Jaswin; Rajendran Lakshmidevi; Sailendra Bhaskar; Senthil Chinnasamy (Journal of Applied Phycology, 2016)

MiSeq HV4 16S rRNA gene analysis of bacterial community composition among the cave sediments of Indo-Burma biodiversity hotspot - Surajit De Mandal; Zothansanga; Amrita Kumari Panda; Satpal Singh Bisht; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2016)

Isolation and characterization of genomic microsatellite markers for small cardamom (Elettaria cardamomum Maton) for utility in genetic diversity analysis - Anu Cyriac; Ritto Paul; K. Anupama; R. Senthil kumar; T. E. Sheeja; K. Nirmal Babu; V. A. Parthasarathy (Physiology and Molecular Biology of Plants, 2016)

Modulation of indole ring annulation in ergoline template: chemistry, receptor binding and in vivo pharmacology with 6-OHDA model of Parkinson’s disease - J. B. Senthil Kumar; Rita Kumari; Pratibha Mehta Luthra (Medicinal Chemistry Research, 2016)

High Spatial and Spectral Details Retention Fusion and Evaluation - C. V. Rao; J. Malleswara Rao; A. Senthil Kumar; D. S. Jain; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2016)

In vitro regeneration by callus culture of Anoectochilus elatus Lindley, an endangered terrestrial jewel orchid - N. Ahamed Sherif; T. Senthil Kumar; M. V. Rao (In Vitro Cellular & Developmental Biology - Plant, 2016)

Relevance of GSTM1, GSTT1 and GSTP1 Gene Polymorphism to Breast Cancer Susceptibility in Mizoram Population, Northeast India - Lalro Kimi; Souvik Ghatak; Ravi Prakash Yadav; Lalhma Chhuani; Doris Lallawmzuali; Jeremy L. Pautu; Nachimuthu Senthil Kumar (Biochemical Genetics, 2016)

Mass propagation of Plectranthus bourneae Gamble through indirect organogenesis from leaf and internode explants - R. Thaniarasu; T. Senthil Kumar; M. V. Rao (Physiology and Molecular Biology of Plants, 2016)

Synthesis of silver and gold nanoparticles using Jasminum nervosum leaf extract and its larvicidal activity against filarial and arboviral vector Culex quinquefasciatus Say (Diptera: Culicidae) - H. Lallawmawma; Gnanasekar Sathishkumar; Subburayan Sarathbabu; Souvik Ghatak; Sivaperumal Sivaramakrishnan; Guruswami Gurusubramanian; Nachimuthu Senthil Kumar (Environmental Science and Pollution Research, 2015)

2,3,5-Trimethoxy-4-cresol, an anti-metastatic constituent from the solid-state cultured mycelium of Antrodia cinnamomea and its mechanism - Chin-Chung Lin; Ching-Chun Chen; Yueh-Hsiung Kuo; Jong-Tar Kuo; K. J. Senthil Kumar; Sheng-Yang Wang (Journal of Natural Medicines, 2015)

Morphological and Molecular Characterization of High Biomass IGH, ISH and Saccharum Hybrids - S. Senthil Kumar; P. Govindaraj; C. Appunu (Sugar Tech, 2015)

Pharmacokinetics of Enrofloxacin in Emu (Dromaius novaehollandiae) Birds After Intravenous and Oral Bolus Administration - P. Senthil Kumar; A. Arivuchelvan; A. Jagadeeswaran; N. Punniamurthy; P. Selvaraj; P. N. Richard Jagatheesan; P. Mekala (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Industrial Fluorosis and Its Effects on Serum Biochemistry and Haemogram in Cattle of Kerala, India - P. Senthil Kumar; C. M. Aravindakshan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

In silico docking studies of non-azadirachtin limonoids against ecdysone receptor of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) - Ravi Prakash Yadav; Kalibulla Syed Ibrahim; Guruswami Gurusubramanian; Nachimuthu Senthil Kumar (Medicinal Chemistry Research, 2015)

Isolation and characterization of a Lecanicillium psalliotae isolate infecting cardamom thrips (Sciothrips cardamomi) in India - C. M. Senthil Kumar; T. K. Jacob; S. Devasahayam; Sharon D’Silva; N. K. Krishna Kumar (BioControl, 2015)

Single strain infection of adult and larval cardamom thrips ( Sciothrips cardamomi ) by Wolbachia subgroup Con belonging to supergroup B in India - T.K. Jacob; Sharon D′Silva; C.M. Senthil Kumar; S. Devasahayam; V. Rajalakshmi; E.S. Sujeesh; A. Ishwara Bhat; Siljo Abraham (Invertebrate Reproduction & Development, 2015)

Recycling of finished leather wastes: a novel approach - Rethinam Senthil; Thiagarajan Hemalatha; Baskar Santhosh Kumar; Tiruchirapalli Sivagnanam Uma; Bhabendra Nath Das; Thotapalli Parvathaleswara Sastry (Clean Technologies and Environmental Policy, 2015)

Fast spatiotemporal data fusion: merging LISS III with AWiFS sensor data - C.V. Rao; J. Malleswara Rao; A. Senthil Kumar; V.K. Dadhwal (International Journal of Remote Sensing, 2014)

Generation of Vegetation Fraction and Surface Albedo Products Over India from Ocean Colour Monitor (OCM) Data Onboard Oceansat-2 - A. Senthil Kumar; T. Radhika; P.K. Saritha; V. Keerthi; R. N. Anjani; M. Suresh Kumar; K. S. Sekhar; P. Satyanarayana; M. S. Naga Sudha; M. V. R. Sesha Sai; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2014)

Geocoding RISAT-1 MRS images using bias-compensated RPC models - K.S.S. Sekhar; A. Senthil Kumar; V.K. Dadhwal (International Journal of Remote Sensing, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Keratin hydrolysate as an exhausting agent in textile reactive dyeing process - Nallathambi Arivithamani; Soloman Agnes Mary; Muthusamy Senthil Kumar; Venkateshwarapuram Rengaswami Giri Dev (Clean Technologies and Environmental Policy, 2014)

Evaluation of groundwater quality in Madurai City, South India for drinking, irrigation and construction purposes - V. Sivasankar; Kiyoshi Omine; T. A. M. Msagati; M. Senthil kumar; A. Chandramohan (Arabian Journal of Geosciences, 2014)

Spectral Deconvolution and Non-Overlap Bands Sampling for IMS-1 Hyperspectral Imager Data - A. Senthil Kumar; T. Radhika; V. Keerthi; D. S. Jain; V. K. Dadhwal; A. S. Kiran Kumar (Journal of the Indian Society of Remote Sensing, 2014)

Brevibacillus as a biological tool: a short review - Amrita Kumari Panda; Satpal Singh Bisht; Surajit DeMondal; N. Senthil Kumar; G. Gurusubramanian; Ashok Kumar Panigrahi (Antonie van Leeuwenhoek, 2014)

High-resolution seismic imaging of the Sohagpur Gondwana basin, central India: Evidence for syn-sedimentary subsidence and faulting - K Dhanam; P Senthil Kumar; D Mysaiah; P Prabhakara Prasad; T Seshunarayana (Journal of Earth System Science, 2013)

Characterization of Bacillus thuringiensis Cry1 class proteins in relation to their insecticidal action - Brindha Senthil Kumar; Zothansanga Ralte; Ajit Kumar Passari; Vineet Kumar Mishra; Biku Moni Chutia; Bhim Pratap Singh; Gurusubramanian Guruswami; Senthil Kumar Nachimuthu (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Tropical storm off Myanmar coast sweeps reefs in Ritchie’s Archipelago, Andaman - P. Krishnan; Grinson Grinson-George; N. Vikas; Titus Titus-Immanuel; M. P. Goutham-Bharathi; A. Anand; K. Vinod Kumar; S. Senthil Kumar (Environmental Monitoring and Assessment, 2013)

Adsorption of Cu(II), Cd(II) and Ni(II) ions from aqueous solution by unmodified Strychnos potatorum seeds - P. Senthil Kumar; A.S.L. Sai Deepthi; R. Bharani; C. Prabhakaran (European Journal of Environmental and Civil Engineering, 2013)

Wavelet Based Post Classification Change Detection Technique for Urban Growth Monitoring - R. A. Alagu Raja; V. Anand; A. Senthil Kumar; Sandeep Maithani; V. Abhai Kumar (Journal of the Indian Society of Remote Sensing, 2013)

Application of ANN, Fuzzy Logic and Decision Tree Algorithms for the Development of Reservoir Operating Rules - A. R. Senthil kumar; Manish Kumar Goyal; C. S. P. Ojha; R. D. Singh; P. K. Swamee; R. K. Nema (Water Resources Management, 2013)

Hydrogeochemical Modelling for Groundwater in Neyveli Aquifer, Tamil Nadu, India, Using PHREEQC: A Case Study - S. Chidambaram; P. Anandhan; M. V. Prasanna; AL. Ramanathan; K. Srinivasamoorthy; G. Senthil Kumar (Natural Resources Research, 2012)

Regulation of insulin-like growth factors and their binding proteins by thyroid stimulating hormone in human osteoblast-like (SaOS2) cells - G. Ramajayam; R. C. Vignesh; S. Karthikeyan; K. Senthil Kumar; G. D. Karthikeyan; S. Veni; M. Sridhar; J. Arunakaran; M. Michael Aruldhas; N. Srinivasan (Molecular and Cellular Biochemistry, 2012)

Cobalt mediated ring contraction reaction of lapachol and initial antibacterial evaluation of naphthoquinones derived from lapachol - Kenneth O. Eyong; Senthil P. Kumar; Victor Kuete; Gabriel N. Folefoc; Henrietta Langmi; Marion J. J. Meyer; Namrita Lall; Sundarababu Baskaran (Medicinal Chemistry Research, 2012)

Identification and characterization of stress resistance related genes of Brassica rapa - Nasar Uddin Ahmed; Jong-In Park; Hee-Jeong Jung; Mi-Suk Seo; Thamilarasan Senthil Kumar; In-Ho Lee; Ill-Sup Nou (Biotechnology Letters, 2012)

Identification and expression analysis of chitinase genes related to biotic stress resistance in Brassica - Nasar Uddin Ahmed; Jong-In Park; Mi-Suk Seo; Thamilarasan Senthil Kumar; In-Ho Lee; Beom-Seok Park; Ill-Sup Nou (Molecular Biology Reports, 2012)

Neem based Integrated Approaches for the Management of Tea Thrips Scirtothrips dorsalis Hood (Thripidae: Thysanoptera) in Tea - Somnath Roy; Guruswami Gurusubramanian; Senthil Kumar Nachimuthu (Proceedings of the Zoological Society, 2011)

Nephroprotective and antioxidant activities of Salacia oblonga on acetaminophen-induced toxicity in rats - S. Palani; S. Raja; S. Nirmal Kumar; B. Senthil Kumar (Natural Product Research, 2011)

Cytotoxic effect of a polymer–copper(II) complex containing 2,2′-bipyridyl ligand on human lung cancer cells - R. Senthil Kumar; V. S. Periasamy; C. Preethy Paul; A. Riyasdeen; S. Arunachalam; M. A. Akbarsha (Medicinal Chemistry Research, 2011)

First record of the entomopathogenic fungus Entomophaga aulicae on the Bihar hairy caterpillar Spilarctia obliqua in Manipur, India - C. M. Senthil Kumar; K. Jeyaram; H. Birkumar Singh (Phytoparasitica, 2011)

Hydrogeochemical assessment of groundwater in Neyveli Basin, Cuddalore District, South India - M. V. Prasanna; S. Chidambaram; G. Senthil Kumar; AL Ramanathan; H. C. Nainwal (Arabian Journal of Geosciences, 2011)

Comparative 3D QSAR study on β1-, β2-, and β3-adrenoceptor agonists - P. Senthil Kumar; Prasad V. Bharatam (Medicinal Chemistry Research, 2010)

Soil-gas helium and surface-waves detection of fault zones in granitic bedrock - G. K. Reddy; T. Seshunarayana; Rajeev Menon; P. Senthil Kumar (Journal of Earth System Science, 2010)

Magnetic fabrics indicating Late Quaternary seismicity in the Himalayan foothills - R. Jayangondaperumal; Ashok Kumar Dubey; B. Senthil Kumar; S. G. Wesnousky; S. J. Sangode (International Journal of Earth Sciences, 2010)

Chemical constituents and antibacterial activity of the leaf essential oil of Feronia limonia - A. Senthil Kumar; V. Venkatesalu; K. Kannathasan; M. Chandrasekaran (Indian Journal of Microbiology, 2010)

Precursory signals using satellite and ground data associated with the Wenchuan Earthquake of 12 May 2008 - Ramesh P. Singh; Waseem Mehdi; Ritesh Gautam; J. Senthil Kumar; Jacques Zlotnicki; Menas Kafatos (International Journal of Remote Sensing, 2010)

In vitro root culture of Ocimum sanctum L. and evaluation of its free radical scavenging activity - Kusampudi Shilpa; Chinnasamy Selvakkumar; Arun Kumar Senthil; Baddireddi Subhadra Lakshmi (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Molecular mapping and location of QTLs for drought-resistance traits in indica rice (Oryza sativa L.) lines adapted to target environments - Selvaraj Michael Gomez; N. Manikanda Boopathi; S. Satheesh Kumar; T. Ramasubramanian; Zhu Chengsong; P. Jeyaprakash; A. Senthil; R. Chandra Babu (Acta Physiologiae Plantarum, 2010)

Mass Loadings of Triclosan and Triclocarbon from Four Wastewater Treatment Plants to Three Rivers and Landfill in Savannah, Georgia, USA - Kurunthachalam Senthil Kumar; S. Mahalakshmi Priya; Aaron M. Peck; Kenneth S. Sajwan (Archives of Environmental Contamination and Toxicology, 2010)

Molecular characterization of Jatropha genetic resources through inter-simple sequence repeat (ISSR) markers - R. Senthil Kumar; K. T. Parthiban; M. Govinda Rao (Molecular Biology Reports, 2009)

Wavelet frame-based feature extraction technique for improving classification accuracy - R. A. Alagu Raja; V. Anand; S. Maithani; A. Senthil Kumar; V. Abhai Kumar (Journal of the Indian Society of Remote Sensing, 2009)

Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut - Geetha Govind; Vokkaliga ThammeGowda Harshavardhan; Jayaker Kalaiarasi Patricia; Ramachandra Dhanalakshmi; Muthappa Senthil Kumar; Nese Sreenivasulu; Makarla Udayakumar (Molecular Genetics and Genomics, 2009)

Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut - Geetha Govind; Harshavardhan Vokkaliga ThammeGowda; Patricia Jayaker Kalaiarasi; Dhanalakshmi Ramchandra Iyer; Senthil Kumar Muthappa; Sreenivasulu Nese; Udaya Kumar Makarla (Molecular Genetics and Genomics, 2009)

Farming of spiny lobsters in sea cages in India - M. Vijayakumaran; R. Venkatesan; T. Senthil Murugan; T.S. Kumar; Dilip Kumar Jha; M.C. Remany; J. Mary Leema Thilakam; S. Syed Jahan; G. Dharani; S. Kathiroli; K. Selvan (New Zealand Journal of Marine and Freshwater Research, 2009)
Pueruli and post‐pueruli, early juveniles and sub‐adults of the spiny lobster, Panulirus homarus and juveniles of P. ornatus were grown in different floating sea cages along the southeast coast of India from May 2003 to May 2007. The first type of cage had a galvanised iron pipe frame (2.0 m × 2.0 m × 1.2 m) with steel woven mesh and four inner detachable compartments (0.75 m × 0.75 m × 1.10 m). Fibre‐reinforced plastic was used subsequently to fabricate cages (1 m × 1 m × 1 m). Pueruli and post‐pueruli of P. homarus (1.58 ± 0.62 g SD), stocked at 60 individuals/m 2 , grew to an average weight of 123.10 ± 26.22 g in 266 days with a survival rate of 70%. Sub‐adults of P. homarus with an average weight (± SD) of 123.61 ± 29.26 g reached 341.25 ± 46.22 g in 225 days at a stocking density of 21 individuals/m 2 with a survival of 73 ± 6%. The post‐pueruli grew by 0.46 ± 0.10 g per day with a specific growth rate (SGR) of 1.64, whereas sub‐adults had a growth rate of 0.97 ± 0.20 g per day with a SGR of 0.43. At a higher stocking density of 80 individuals/m 2 , juveniles (51.83 ± 10.32 g and 58.20 ± 28.22 g) of P. homarus recorded growth rates of 0.86 ± 0.25 (SGR 0.82) and 0.97 ± 0.34 g (SGR 0.96) per day. This study indicates that post‐pueruli of P. homarus can be grown to over 200 g in 12 months and up to 350 g in 16 to 17 months in sea cages. Juveniles (average weight 76.35 ± 34.50 g) of P. ornatus , reared with P. homarus at a stocking density of 80 individuals/m 2 , recorded a weight gain of 139 g in 155 days at arate of 0.89 ± 0.32 g per day with an SGR of 0.67. Marine live clam, Donax spp., was the main feed supplemented with the gastropod, Xancus pyrum , the green mussel, Perna viridis , marine crab (Charibdis sp.), squid (Loligo sp.), and fish such as clupeids and Leognathus sp. Pueruli and post‐pueruli settled in large numbers (up to 35 individuals/month in one cage) both inside and outside the cages.

Deposition of Organochlorine Pesticides, PCBs (Aroclor 1268), and PBDEs in Selected Plant Species from a Superfund Site at Brunswick, Georgia, USA - Kenneth S. Sajwan; Kurunthachalam Senthil Kumar; Sarah Kelley; Bommanna G. Loganathan (Bulletin of Environmental Contamination and Toxicology, 2009)

Octamer and heat shock elements regulate transcription from the AcMNPV polyhedrin gene promoter - M. Senthil Kumar; Aruna Ramachandran; Seyed E. Hasnain; Murali Dharan Bashyam (Archives of Virology, 2009)

Captive breeding and larval development of the scyllarine lobster Petrarctus rugosus - T.S. Kumar; M. Vijayakumaran; T. Senthil Murugan; Dilip Kumar Jha; G. Sreeraj; S. Muthukumar (New Zealand Journal of Marine and Freshwater Research, 2009)
The scyllarinid lobster, Petrarctus rugosus was reared to the postlarval nisto in 51 days at 24.9–26.5°C between November 2003 and April 2004 in Chennai, India. The lobster had eight phyllosomal instars. The eighth instars died while moulting to nisto. Instar VI was attained in 34 days with an average intermoult period of 5.4 days, whereas the last two moults took 17 days to complete. The captive breeders mated and bred several times between November and April with peak spawning in February. Repetitive breeding was observed with the brooding period varying from 11 to 17 days. Mean fecundity was 17 004 eggs ± 11 486 (SD). Hatching percentage was between 0.00 and 87.44.

Additive interaction of Helicoverpa armigera Nucleopolyhedrovirus and Azadirachtin - Nachimuthu Senthil Kumar; Kadarkarai Murugan; Wenqing Zhang (BioControl, 2008)

Purification and characterization of an extracellular keratinase from a hornmeal-degrading Bacillus subtilis MTCC (9102) - S. Balaji; M. Senthil Kumar; R. Karthikeyan; Ramadhar Kumar; S. Kirubanandan; R. Sridhar; P. K. Sehgal (World Journal of Microbiology and Biotechnology, 2008)

Genetic diversity among Jatropha species as revealed by RAPD markers - S. Ganesh Ram; K. T. Parthiban; R. Senthil Kumar; V. Thiruvengadam; M. Paramathma (Genetic Resources and Crop Evolution, 2008)

Influence of zinc on cadmium induced haematological and biochemical responses in a freshwater teleost fish Catla catla - Sweety R. Remyla; Mathan Ramesh; Kenneth S. Sajwan; Kurunthachalam Senthil Kumar (Fish Physiology and Biochemistry, 2008)

Distribution of Persistent Organohalogen Compounds in Pine Needles from Selected Locations in Kentucky and Georgia, USA - Bommanna G. Loganathan; Kurunthachalam Senthil Kumar; Kosta D. Seaford; Kenneth S. Sajwan; Nobuyasu Hanari; Nobuyoshi Yamashita (Archives of Environmental Contamination and Toxicology, 2008)

Occurrence, distribution and economic potential of seashore mangosteen (Garcinia hombroniana Pierre) in India - K. Joseph John; R. Senthil Kumar; C. P. Suresh; Johnson K. George; Z. Abraham (Genetic Resources and Crop Evolution, 2008)

Elemental Status in Sediment and American Oyster Collected from Savannah Marsh/Estuarine Ecosystem: A Preliminary Assessment - Kenneth S. Sajwan; Kurunthachalam Senthil Kumar; Sivapatham Paramasivam; Sanya S. Compton; Joseph P. Richardson (Archives of Environmental Contamination and Toxicology, 2008)

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans, and Dioxin-Like Polychlorinated Biphenyls in Sediment and Mussel Samples from Kentucky Lake, USA - Bommanna G. Loganathan; Kurunthachalam Senthil Kumar; Shigeki Masunaga; Kenneth S. Sajwan (Archives of Environmental Contamination and Toxicology, 2008)

Isolation and characterization of endophytic bacteria from wild and cultivated soybean varieties - Pham Q. Hung; Senthil M. Kumar; V. Govindsamy; K. Annapurna (Biology and Fertility of Soils, 2007)

Chlamydomonas reinhardtii, a model system for functional validation of abiotic stress responsive genes - R. Hema; M. Senthil-Kumar; S. Shivakumar; P. Chandrasekhara Reddy; M. Udayakumar (Planta, 2007)

Molecular Cloning, Characterization, and Expression of a Chitinase from the Entomopathogenic Fungus Paecilomyces javanicus - Chien-Cheng Chen; H.G. Ashok Kumar; Senthil Kumar; Shean-Shong Tzean; Kai-Wun Yeh (Current Microbiology, 2007)

Role of Temperature and Hydrochloric Acid on the Formation of Chlorinated Hydrocarbons and Polycyclic Aromatic Hydrocarbons During Combustion of Paraffin Powder, Polymers, and Newspaper - Takumi Takasuga; Norihito Umetsu; Tetsuya Makino; Katsuya Tsubota; Kenneth S. Sajwan; Kurunthachalam Senthil Kumar (Archives of Environmental Contamination and Toxicology, 2007)

Effect of dust storm on ocean color and snow parameters - Vinay K. Kayetha; Senthil Kumar J.; Anup K. Prasad; Guido Cervone; Ramesh P. Singh (Journal of the Indian Society of Remote Sensing, 2007)

Assessment of Genetic Diversity among Finger Millet (Eleusine coracana (L.) Gaertn.) Accessions using Molecular Markers - B. Kalyana Babu; N. Senthil; S. Michael Gomez; K. R. Biji; N. S. Rajendraprasad; S. Satheesh Kumar; R. Chandra Babu (Genetic Resources and Crop Evolution, 2007)

Functional characterization of Nicotiana benthamiana homologs of peanut water deficit-induced genes by virus-induced gene silencing - M. Senthil-Kumar; Geetha Govind; Li Kang; Kirankumar S. Mysore; M. Udayakumar (Planta, 2007)

Biological activity and characterization of nucleopolyhedrovirus isolates ofSpodoptera litura - C. M. Senthil Kumar; R. J. Rabindra; N. Sathiah (Phytoparasitica, 2006)

Synergistic interactions of Ferulic acid with Ascorbic acid: Its cardioprotective role during isoproterenol induced myocardial infarction in rats - Surinder Kumar Yogeeta; Arunachalam Gnanapragasam; Subramanian Senthil Kumar; Rajakannu Subhashini; Arumugam Sathivel; Thiruvengadum Devaki (Molecular and Cellular Biochemistry, 2006)

Chemical Characterization of Polychlorinated Biphenyls, -Dibenzo-p-Dioxins, and -Dibenzofurans in Technical Kanechlor PCB Formulations in Japan - Takumi Takasuga; Kurunthachalam Senthil Kumar; Yukio Noma; Shinichi Sakai (Archives of Environmental Contamination and Toxicology, 2005)

Analysis of UNEP Priority POPs Using HRGC-HRMS and Their Contamination Profiles in Livers and Eggs of Great Cormorants (Phalacrocorax carbo) from Japan - Kurunthachalam Senthil Kumar; Kiyohiko Watanabe; Hiroaki Takemori; Naomasa Iseki; Shigeki Masunaga; Takumi Takasuga (Archives of Environmental Contamination and Toxicology, 2005)

Growth, repetitive breeding, and aquaculture potential of the spiny lobster, Panulirus ornatus - T. Senthil Murugan; M. C. Remany; T. Mary Leema; JHA Dilip Kumar; J. Santhanakumar; M. Vijayakumaran; R. Venkatesan; M. Ravindran (New Zealand Journal of Marine and Freshwater Research, 2005)
A pair of subadult Panulirus ornatus was reared in the laboratory from July 2001. The female grew from 0.6 to 1.3 kg and the male from 0.5 to 1.6 kg in 2 years before the first mating in July 2003. In 6 months, from July to December 2003, the pair mated and spawned 3 times, producing 1.6 million eggs and 1.1 million phyllosoma larvae. Mating occurred 25 and 63 days after moulting. The female spawned 2–3 days after mating and the incubation time ranged from 23 to 27 days. The phyllosoma larvae were released over 2 successive days. The growth rate reduced after first mating in both the male and female and the female expended 42% of the total weight gain for egg production.

Captive breeding of the spiny lobster, Panulirus homarus - M. Vijayakumaran; T. Senthil Murugan; M. C. Remany; T. Mary Leema; J. Dilip Kumar; J. Santhanakumar; R. Venkatesan; M. Ravindran (New Zealand Journal of Marine and Freshwater Research, 2005)
Captive broodstock of the spiny lobster, Panulirus homarus, mated successfully and produced more than 105 spawnings over 4 years. Improvements in nutrition and rearing conditions increased the number of spawnings from less than 2, to 4 per year. A single breeder mates three or more times in a year and may spawn more than once following a single mating. An average of four repetitive spawnings per year was recorded. One third of the females spawned 5 times and a single female spawned 7 times in one year. The phyllosoma were released in one or two batches on successive days. The number of phyllosoma larvae released varied from 16 000 to 529 180 with breeder weights ranging from 218 to 696 g.

Temporal Trends of Organochlorine Pesticides in Prawn (Macrobrachium nipponense) from Lake Kasumigaura, Japan, During 1978?2000 - Sunardi; K. Senthil Kumar; S. Masunaga; N. Iseki; S. Kasuga; J. Nakanishi (Archives of Environmental Contamination and Toxicology, 2004)

Formation of Polychlorinated Naphthalenes, Dibenzo-p-Dioxins, Dibenzofurans, Biphenyls, and Organochlorine Pesticides in Thermal Processes and Their Occurrence in Ambient Air - Takumi Takasuga; Tsuyoshi Inoue; Etsumasa Ohi; Kurunthachalam Senthil Kumar (Archives of Environmental Contamination and Toxicology, 2004)

Immunobiology of trophoblast cells - Chandana Das; V. Senthil Kumar; Sayantani Basak; Surabhi Gupta; Sunesh Kumar (Indian Journal of Clinical Biochemistry, 2000)

Influence of Helicoverpa Armigera (Hübner) Diet on Its Parasitoid Campoletis Chlorideae Uchida - K. Murugan; N. Senthil Kumar; D. Jeyabalan; S. Senthil Nathan; S. Sivaramakrishnan; M. Swamiappan (International Journal of Tropical Insect Science, 2000)

Potentiating Effects of Neem on Nucleopolyhedrovirus Treatment of Spodoptera litura Fab. - K. Murugan; S. Sivaramakrishnan; N. Senthil Kumar; D. Jeyabalan; S. Senthil Nathan (International Journal of Tropical Insect Science, 1999)

Antifeedant and Growth-Inhibitory Properties of Neem Limonoids against the Cotton Bollworm, Helicoverpa armigera (Hübner) - K. Murugan; D. Jeyabalan; N. Senthil Kumar; R. Babu; S. Sivaramakrishnan; S. Senthil Nathan (International Journal of Tropical Insect Science, 1998)